Rubber product made from pyrolysis oil via polymerization
By polymerizing the energy-polymerized components in the pyrolytic oil, an oligomeric product or liquid resin is generated, which solves the problem of difficulty in increasing the value of pyrolytic plastic oil and achieves the improvement of the performance of the rubber composition.
Patent Information
- Application Number
- CN202380053751.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-14
- Filing Date
- 2023-07-13
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively add value to the pyrolytic plastic oil, especially because it contains a large amount of impurities and olefin compounds, limiting its value in rubber applications.
By polymerizing the energy polymerization components in the oil, especially cationic polymerization using the Fuke catalyst, an oligomeric product or liquid resin is produced, which has low viscosity and aromatic content, suitable for use in rubber compositions.
The value-added of pyrolytic plastic oil is achieved, and the resulting oligomeric product can improve the performance of the rubber composition, including the improvement of silica dispersion, wet traction and rolling resistance.
Smart Images

Figure BDA0005241235900000131 
Figure BDA0005241235900000401 
Figure BDA0005241235900000421
Abstract
Description
Technical Field
[0001] The present disclosure relates to the preparation of oligomeric products or liquid resins, prepared via the polymerization of pyrolysis oil (cracking oil, thermal cracking oil, pyrolysis oil). The present disclosure also relates to rubber compositions comprising the oligomeric products or liquid resins. In particular, the present disclosure relates to the polymerization of polymerizable components in pyrolysis oil, preferably via the polymerization of oils preferably obtained by pyrolysis of plastics, so as to obtain oligomeric products, which can be further used in rubber applications. Background Art
[0002] Most of the discarded plastics are transferred to landfills or incinerated, with a smaller portion being transferred to recycling. However, due to the impact of regulations, there is a strong demand to limit the discarded plastics in landfills. On the other hand, the disposal of discarded plastics in landfills is becoming increasingly difficult. Therefore, there is a need for recycled discarded plastics.
[0003] A possible route for recycling plastics is via plastic pyrolysis. However, pyrolysis plastic oil obtained from plastic pyrolysis is generally not easy to value-add. Pyrolysis plastic oil contains a large amount of impurities and a large amount of dienes and olefins.
[0004] FR 3,116,279 relates to a process for producing hydrocarbon resins from a raw material containing rubber crumbs, said process comprising at least one pyrolysis step and a resin synthesis step.
[0005] US2016 / 369015 relates to a backbone-modified elastomeric polymer and to a polymer composition comprising such a modified polymer, to the use of such a composition in preparing a vulcanized polymer composition, and to articles prepared therefrom. The modified polymer can be used to prepare a vulcanized (i.e., cross-linked) elastomeric composition having relatively low hysteresis loss.
[0006] US2020 / 377700 relates to a sulfur-crosslinkable rubber mixture, a vulcanizate thereof and a vehicle tire. The sulfur-crosslinkable rubber mixture contains at least the following components: at least one diene rubber; and 10 to 300 phr of at least one silicic acid; 1 to 30 phr of at least one silane of a specific formula; and 0.5 to 30 phr of at least one silane of a specific formula.
[0007] There is therefore a need for the valorization of those pyrolyzed plastic oils. More precisely, there is clearly a need for the valorization of polymerizable materials present in the pyrolyzed plastic oils. Summary of the invention
[0008] The object of the present disclosure is to provide a value-added route for olefins, dienes and other polymerizable materials present in pyrolysis oil. More specifically, the object of the present disclosure is to convert the polymerizable components present in pyrolysis oil into valuable oligomeric products via polymerization. In particular, it has been found that rubber compositions can be produced from liquid resins prepared from liquefied waste polymers; wherein the liquid resin is an oligomeric product that can be liquid at ambient temperature.
[0009] Surprisingly, when used in a tire, a rubber composition comprising such an oligomeric product allows for improvements in tire performance of at least one of silica dispersion, wet traction and rolling resistance. The present disclosure is directed to valorization of olefins and dienes present in pyrolyzed plastic oils and to providing rubber compositions that allow for improvements in at least one of silica dispersion, wet traction and rolling resistance.
[0010] It has been found that the oligomeric product prepared by pyrolysis oil and especially by pyrolysis plastic oil is particularly advantageous.In fact, such oligomeric product presents relatively low viscosity.Under the situation of low viscosity, it is easier to handle (transport) oligomeric product, making it easier to mix oligomeric product with other components and use less mechanical energy to mix described oligomeric product with other components.Another advantage of oligomeric product is its aromatic content, improves the compatibility of some other components of oligomeric product and rubber combination.
[0011] According to a first aspect, the present disclosure relates to a rubber composition comprising:
[0012] a) at least one elastomer selected from synthetic elastomers and natural elastomers;
[0013] b) a curing agent; and
[0014] c) an oligomeric product prepared from liquefied waste polymer, said oligomeric product having a number average molecular weight Mn in the range of 100 to 10 000 g / mol measured using gel permeation chromatography and polystyrene calibration, and wherein said oligomeric product exhibits a crystallization temperature below 35°C, or a glass transition temperature (Tg) below -20°C when determined by differential scanning calorimetry.
[0015] In some embodiments, the content of the at least one elastomer in the rubber composition ranges from 1 to 150 phr; preferably, from 1 to 120 phr; more preferably, from 1 to 100 phr; from 50 to 150 phr.
[0016] In some embodiments, the content of the curing agent in the rubber composition ranges from 0.1-25 phr; preferably, 0.5 to 22 phr; more preferably 1 to 20 phr, and even more preferably 5 to 18 phr.
[0017] In some embodiments, the content of the oligomeric product in the rubber composition ranges from 0.1 to 50 phr; preferably, from 0.5 to 40 phr; more preferably, from 1 to 30 phr, and even more preferably, from 5 to 25 phr.
[0018] In some embodiments, when 1 When measured by H NMR, the oligomeric product shows an olefin content of up to 20.0 wt%. Preferably, the olefin content of the liquid resin ranges from 0.1 to 20.0 wt%; preferably 0.3 to 15.0 wt%; more preferably 0.5 to 10.0 wt%, 0.8 to 5.0 wt%.
[0019] In some embodiments, when 1 When measured by H NMR, the oligomeric product exhibits an aliphatic content ranging from 15 to 100 wt %; preferably ranging from 40.0 to 99.5 wt %; more preferably ranging from 50.0 to 99.0 wt %; even more preferably ranging from 70.0 to 98.5 wt %; and most preferably ranging from 80.0 to 98.0 wt %.
[0020] In one or more embodiments, when 1 When measured by H NMR, the oligomeric product exhibits an aromatic content in the range of 0.3 to 45.0 wt %; preferably in the range of 0.5 to 40.0 wt %; more preferably in the range of 0.8 to 30.0 wt %; and even more preferably in the range of 1.0 to 20.0 wt %.
[0021] In an embodiment, the oligomeric product has a viscosity at 30°C measured using a Brookfield viscometer ranging from 10 to 50,000 cps; preferably ranging from 10 to 50,000 cps; more preferably ranging from 10 to 10,000 cps; even more preferably ranging from 10 to 4000 cps; and most preferably ranging from 10 to 2500 cps.
[0022] In some embodiments, the oligomeric product has a number average molecular weight (Mn) in the range of 100 to 10,000 g / mol; preferably 120 to 5,000 g / mol; more preferably 140 to 1,000 g / mol; even more preferably 150 to 800 g / mol; most preferably 180 to 700 g / mol; or 200 to 650 g / mol; or 250 to 550 g / mol as measured using gel permeation chromatography and polystyrene calibration.
[0023] In some embodiments, the oligomeric product has a weight average molecular weight (Mw) ranging from 100 to 10,000 g / mol; preferably 120 to 5,000 g / mol; more preferably 150 to 3,500 g / mol; and even more preferably 200 to 2,000 g / mol as measured using gel permeation chromatography and polystyrene calibration.
[0024] In some embodiments, the oligomeric product has a z-average molecular weight (Mz) ranging from 100 to 100,000 g / mol; preferably 120 to 85,000 g / mol; more preferably 150 to 70,000 g / mol; and even more preferably 200 to 50,000 g / mol as measured using gel permeation chromatography and polystyrene calibration.
[0025] In some embodiments, the oligomeric product has a Mw / Mn ranging from 1.0 to 10.0; preferably 1.0 to 5.0; more preferably 1.0 to 4.0; and even more preferably 1.1 to 2.8.
[0026] In a preferred embodiment, the oligomeric product comprises a comonomer selected from the group consisting of styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-tert-butylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2,4-diisopropylstyrene, 2,4,6-trimethylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, 1-vinylnaphthalene, 2-vinylnaphthalene, vinylanthracene, 4-methoxystyrene, monochlorostyrene, dichlorostyrene, divinylbenzene, indene, methyl-indene, and mixtures thereof; preferably, the liquid resin (i.e., the oligomeric product) comprises a comonomer, and the comonomer is or comprises styrene.
[0027] In an embodiment, the oligomeric product comprises the comonomer present in a concentration ranging from 0.01 to 90 mol %, preferably 1.0 to 80 mol %, based on the total weight of the liquid resin.
[0028] In some embodiments, the oligomeric product is a wax and / or exhibits a crystallization temperature (Tc) below 35°C; preferably in the range of 18 to 32°C; more preferably in the range of 20 to 30°C; and even more preferably in the range of 21 to 29°C.
[0029] In an embodiment, the oligomeric product is a resin and / or exhibits a glass transition temperature (Tg) of below -20°C; preferably in the range of -60°C to -25°C; more preferably -50°C to -30°C; and even more preferably -49°C to -35°C when measured by differential scanning calorimetry.
[0030] According to a second aspect, the present disclosure provides a tire comprising the rubber composition according to the first aspect, preferably comprising the oligomeric product in a content ranging from 1 to 50 phr.
[0031] According to a third aspect, the present disclosure provides a process for preparing the rubber composition according to the first aspect, the process comprising the following steps:
[0032] a) providing a feed stream comprising liquefied waste polymer, wherein the feed stream comprises at least 0.1 wt % and at most 80 wt % diene, based on the total weight of the feed stream;
[0033] c) polymerizing the feed stream under polymerization conditions to obtain a first product stream comprising oligomeric products and purified liquefied waste polymer;
[0034] d) optionally, conducting a neutralization reaction by contacting the first product stream with a basic compound to obtain a neutralized product stream, and removing the basic compound from the neutralized product stream to obtain a second product stream;
[0035] g) separating the oligomeric products from the purified liquefied waste polymer; and
[0036] h) preparing a rubber composition comprising: at least one elastomer selected from synthetic elastomers and natural elastomers; a curing agent; and the oligomeric product recovered in step g).
[0037] In some embodiments, the liquefied waste polymer is pyrolyzed plastic oil. Preferably, step a) of providing a feed stream containing the liquefied waste polymer comprises a preliminary step of preparing the liquefied waste polymer, comprising:
[0038] a1) Provide waste plastic streams;
[0039] a2) pyrolyzing the waste plastic stream at a temperature of at least 200° C.;
[0040] a3) collecting the pyrolyzer effluent and separating it into a C1 to C4 hydrocarbon fraction, a fraction having a boiling range above 350° C., and a remaining fraction as the pyrolyzed plastic oil;
[0041] a4) optionally sending the fraction with a boiling range above 350°C to a fluid catalytic cracking (FCC) unit, or a hydrocracking unit, a coker, or a visbreaker, or blending said fraction with a boiling range above 350°C in crude oil or in crude oil fractions for further refining.
[0042] In one or more embodiments, the process further comprises a step b) of drying the feed stream to obtain a dried feed stream, wherein step b) is performed before step c) of polymerization, so that step c) of polymerization is performed on the dried feed stream. Preferably, step b) of drying is performed and it includes a sub-step b1) of decantation and / or centrifugation. More preferably, the first sub-step b1) is followed by a second sub-step b2) of drying using molecular sieves to reach a water content of less than 0.1% by volume according to ASTM D95-13 (2018).
[0043] In some embodiments, the feed stream contains at least 75 weight percent liquefied waste polymer, based on the total weight of the feed stream.
[0044] Step c) comprises carrying out a polymerization reaction, preferably a cationic polymerization or a free radical polymerization or an anionic polymerization.
[0045] In a preferred embodiment, the polymerization reaction is a cationic polymerization; more preferably, the polymerization reaction in step c) is a cationic polymerization carried out in the presence of an acidic catalyst; preferably, the acidic catalyst is a Bronsted acid or a Lewis acid.
[0046] In a preferred embodiment, the polymerization reaction in step c) is a cationic polymerization carried out in the presence of an acidic catalyst, wherein the acidic catalyst is a Lewis acid selected from BF 3 , boron trifluoride complex, AICl 3 SnCl 4 、ZnCl 2 、FeCl 3 and TiCl 3 , alkylaluminum chloride, H 2 SO 4 , or any mixture thereof; preferably, the acidic catalyst is or comprises boron trifluoride etherate.
[0047] In an embodiment, the process of the acidic catalyst is present in a concentration ranging from 0.5 wt % to 5.0 wt %, based on the total weight of the feed stream and / or the polymerization reaction of step c) is carried out until the purified liquefied waste polymer has less than 5.0 wt % diene, based on the total weight of the first product stream.
[0048] In a preferred embodiment, the polymerization conditions of step (c) include a contact time ranging from 5 minutes to 5 hours; and / or a temperature ranging from 5 to 100°C at atmospheric pressure.
[0049] In an embodiment, the polymerization reaction of step c) is carried out in the presence of one or more comonomers; preferably, the one or more comonomers comprise vinyl aromatic and / or the one or more comonomers are present in a concentration of 1.0 to 25.0 weight %, based on the total weight of the liquefied waste polymer.
[0050] In some embodiments, the basic compound forms a basic stream; wherein the basic stream and the first product stream are contacted in a weight ratio ranging from 1:1 to 1:1,000.
[0051] In some embodiments, step d) is performed with a concentration of the basic compound ranging from 0.1 to 50.0 wt %, based on the total weight of the neutralized product stream.
[0052] In a preferred embodiment, step d) is performed and the basic compound:
[0053] - has a pKa in water ranging from 7.5 to 14; and / or
[0054] -Selected from LiOH, NaOH, CsOH, Ba(OH) 2 、Na 2 O, KOH, K 2 O, CaO, Ca(OH) 2 、MgO、Mg(OH) 2 NH 4 OH, or any mixture thereof.
[0055] In an embodiment, step d) is performed in a continuous mode; and / or removing said basic compound from the neutralized product stream, to obtain a second product stream, is performed by decantation and / or by centrifugation.
[0056] In an embodiment, the process further comprises a step e) of washing the first product stream or the second product stream with a solvent to obtain a washed stream; preferably, the washing is carried out at a temperature ranging from 5°C to 95°C.
[0057] In a preferred embodiment, the solvent is selected from water or an acidic aqueous solution, which comprises:
[0058] - one or more organic acids selected from the group consisting of: citric acid (C 6 H 8 O 7 ), formic acid (CH 2 O 2 ), acetic acid (CH 3 COOH), aminosulfonic acid (H 3 NSO 3 ), and any combination thereof; and / or
[0059] - one or more inorganic acids selected from the group consisting of hydrochloric acid (HCl), nitric acid (HNO 3 ), sulfuric acid (H 2 SO 4 ), phosphoric acid (H 3 PO 4 ), and any combination thereof.
[0060] In some embodiments, washing is performed until the pH of the washed stream is in the range of 5.0 to 9.0; and / or washing is followed by decantation and / or centrifugation to separate the solvent from the washed stream.
[0061] In an embodiment, the process further comprises a step f) of filtering the stream obtained in the previous step to obtain a filtered stream, wherein the filtration is performed to remove solids from the first product stream or from the second product stream or from the washed stream, and / or to agglomerate remaining traces of solvent, if any; preferably, the filtration step is followed by a dehydration step.
[0062] In an embodiment, step g) of separating is performed via distillation or steam distillation or vacuum stripping or fractional distillation or any combination.
[0063] In a preferred embodiment, after separation step g), the purified liquefied waste polymer is collected and blended in a fuel pool; preferably, the purified liquefied waste polymer is separated into a naphtha fraction having a boiling range of less than 150°C and a diesel fraction having a boiling range between 150 and 350°C, wherein the naphtha fraction is incorporated into the naphtha pool and the diesel fraction is incorporated into the diesel pool.
[0064] In a preferred embodiment, the liquefied waste polymer in the feed stream has a final boiling point of at most 700°C.
[0065] In a preferred embodiment, the feed stream contains from 0.1 to 50.0 wt %; preferably from 0.1 to 25.0 wt % diene, based on the total weight of the feed stream.
[0066] In one or more embodiments, the liquefied waste polymer is pyrolysis oil, preferably pyrolysis plastic oil, or any pyrolysis oil prepared from waste plastic, rubber, biomass, used tires, or any mixture thereof.
[0067] According to a fourth aspect, the present disclosure provides an apparatus for carrying out the process described in the third aspect, wherein the apparatus is notable in that it comprises:
[0068] - polymeric part;
[0069] - an optional neutralizing moiety;
[0070] - separation part;
[0071] wherein the polymerization section and the separation section are fluidly connected in series, and wherein the neutralization section, when present, is placed downstream of the polymerization section and upstream of the separation section.
[0072] Preferably, the device comprises:
[0073] - a pretreatment section comprising a pyrolysis unit, one or more separation units, and optionally a washing unit;
[0074] - a drying section comprising a decanter and / or a centrifuge; and / or molecular sieves;
[0075] - a polymerization section, which comprises one or more polymerization reactors; preferably loaded with an acidic catalyst;
[0076] - a neutralization section, a mixing reactor and optionally a separation unit comprising at least one selected from a decanter, a centrifuge and a filter;
[0077] - a washing section comprising a mixing vessel and a separation unit comprising a decanter and / or a centrifuge;
[0078] - A filtration section comprising a filter and optionally a molecular sieve.
[0079] - A separation section comprising a separation unit comprising one or more distillation columns.
[0080] Preferably, the apparatus further comprises a mixing unit to prepare a rubber composition from the oligomeric product recovered from the separation portion. The present disclosure relates to a rubber composition comprising:
[0081] a) at least one elastomer selected from synthetic elastomers and natural elastomers;
[0082] b) a curing agent; and
[0083] c) an oligomeric product prepared from liquefied waste polymer, said oligomeric product having a number average molecular weight Mn in the range of 100 to 10 000 g / mol measured using gel permeation chromatography and polystyrene calibration, and wherein said oligomeric product exhibits a crystallization temperature below 35°C, or a glass transition temperature (Tg) below -20°C when determined by differential scanning calorimetry.
[0084] In some embodiments, the content of the at least one elastomer in the rubber composition ranges from 1 to 150 phr; preferably, from 1 to 120 phr; more preferably, from 1 to 100 phr; from 50 to 150 phr.
[0085] In some embodiments, the content of the curative agent in the rubber composition ranges from 0.1 to 25 phr; preferably, from 0.5 to 22 phr; more preferably, from 1 to 20 phr, and even more preferably, from 5 to 18 phr.
[0086] In some embodiments, the content of the oligomeric product in the rubber composition ranges from 0.1 to 50 phr; preferably, from 0.5 to 40 phr; more preferably from 1 to 30 phr, and even more preferably from 5 to 25 phr.
[0087] In some embodiments, when 1 When measured by H NMR, the oligomeric product shows an olefin content of at most 20.0 wt%. Preferably, the liquid resin has an olefin content in the range of 0.1 to 20.0 wt%; preferably 0.3 to 15.0 wt%; more preferably 0.5 to 10.0 wt%, 0.8 to 5.0 wt%.
[0088] In some embodiments, when 1 When measured by H NMR, the oligomeric product exhibits an aliphatic content ranging from 15 to 100 wt %; preferably ranging from 40.0 to 99.5 wt %; more preferably ranging from 50.0 to 99.0 wt %; even more preferably ranging from 70.0 to 98.5 wt %; and most preferably ranging from 80.0 to 98.0 wt %.
[0089] In one or more embodiments, when 1 When measured by H NMR, the oligomeric product exhibits an aromatic content in the range of 0.3 to 45.0 wt %; preferably in the range of 0.5 to 40.0 wt %; more preferably in the range of 0.8 to 30.0 wt %; and even more preferably in the range of 1.0 to 20.0 wt %.
[0090] In an embodiment, the oligomeric product has a viscosity at 30°C measured using a Brookfield viscometer ranging from 10 to 50,000 cps; preferably ranging from 10 to 50,000 cps; more preferably ranging from 10 to 10,000 cps; even more preferably ranging from 10 to 4000 cps; and most preferably ranging from 10 to 2500 cps.
[0091] In some embodiments, the oligomeric product has a number average molecular weight (Mn) in the range of 100 to 10,000 g / mol; preferably 120 to 5,000 g / mol; more preferably 140 to 1,000 g / mol; even more preferably 150 to 800 g / mol; most preferably 180 to 700 g / mol; or 200 to 650 g / mol; or 250 to 550 g / mol as measured using gel permeation chromatography and polystyrene calibration.
[0092] In some embodiments, the oligomeric product has a weight average molecular weight (Mw) ranging from 100 to 10,000 g / mol; preferably 120 to 5,000 g / mol; more preferably 150 to 3,500 g / mol; and even more preferably 200 to 2,000 g / mol as measured using gel permeation chromatography and polystyrene calibration.
[0093] In some embodiments, the oligomeric product has a z-average molecular weight (Mz) ranging from 100 to 100,000 g / mol; preferably 120 to 85,000 g / mol; more preferably 150 to 70,000 g / mol; and even more preferably 200 to 50,000 g / mol as measured using gel permeation chromatography and polystyrene calibration.
[0094] In some embodiments, the oligomeric product has a Mw / Mn ranging from 1.0 to 10.0; preferably 1.0 to 5.0; more preferably 1.0 to 4.0; and even more preferably 1.1 to 2.8.
[0095] In a preferred embodiment, the oligomeric product comprises a comonomer selected from the group consisting of styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-tert-butylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2,4-diisopropylstyrene, 2,4,6-trimethylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, 1-vinylnaphthalene, 2-vinylnaphthalene, vinylanthracene, 4-methoxystyrene, monochlorostyrene, dichlorostyrene, divinylbenzene, indene, methyl-indene, and mixtures thereof; preferably, the liquid resin (i.e., the oligomeric product) comprises a comonomer, and the comonomer is or comprises styrene.
[0096] In an embodiment, the oligomeric product comprises the comonomer present in a concentration ranging from 0.01 to 90 mol %, preferably 1.0 to 80 mol %, based on the total weight of the liquid resin.
[0097] In some embodiments, the oligomeric product is a wax and / or exhibits a crystallization temperature (Tc) below 35°C; preferably in the range of 18 to 32°C; more preferably in the range of 20 to 30°C; and even more preferably in the range of 21 to 29°C.
[0098] In an embodiment, the oligomeric product is a resin and / or exhibits a glass transition temperature (Tg) of below -20°C; preferably in the range of -60°C to -25°C; more preferably -50°C to -30°C; and even more preferably -49°C to -35°C when measured by differential scanning calorimetry. BRIEF DESCRIPTION OF THE DRAWINGS
[0099] Figure 1 A possible embodiment of the present invention is described. In this possible embodiment, the liquefied waste polymer is first optionally dried and sent to a cationic polymerization to convert dienes into oligomeric products. The effluent of the cationic polymerization is then sent to an optional treatment with an alkaline compound, followed by the removal of the alkaline compound and an optional washing step. After the optional filtering step, the various fractions are separated into various fractions according to boiling points. If the heavy fraction can be separated, it is sent to a conversion unit. The oligomeric products converted into resins can also be separated. If the remaining fraction of the purified plastic oil fraction exists, it can be sent to hydrotreatment or cracking or steam cracking to produce further polymerized olefins. The oligomeric products obtained can also be further used as valuable resins.
[0100] Figure 2 A calibration curve for maleic anhydride concentration is presented.
[0101] Figure 3The 1H NMR olefin content of the treated pyrolysis oil compared to the original pyrolysis oil of Examples 2 to 4 is presented.
[0102] Figure 4 The olefinic carbon stretching peak areas from the FTIR of Examples 2 to 4 are presented.
[0103] Figure 5 An apparatus for preparing oligomeric products is shown.
[0104] Definition and Analytical Methods
[0105] For the purposes of this disclosure, the following definitions are provided:
[0106] The term "alkane" as used herein describes a non-cyclic branched or unbranched hydrocarbon with the general formula CnH2n+2, and is therefore composed entirely of hydrogen atoms and saturated carbon atoms; see, for example, IUPAC. Compendium of Chemical Terminology, 2nd edition (1997). The term "alkane" describes unbranched alkanes ("normal-paraffins" or "n-paraffins" or "n-paraffins" or "paraffins") and branched alkanes ("iso-paraffins" or "iso-paraffins"), but does not include cycloalkanes (cycloalkanes). They are sometimes referred to by the symbol "HC-".
[0107] The term "hydrocarbon" refers to alkanes (saturated hydrocarbons), cycloalkanes, aromatic hydrocarbons and unsaturated hydrocarbons together.
[0108] As used herein, the terms "comprising, comprises, comprised of" are synonymous with "including" or "containing", and are inclusive or open-ended and do not exclude additional, unrecited members, elements or method steps. The term "comprising" also includes the term "consisting of".
[0109] The recitation of numerical ranges by endpoints includes all integers and, where appropriate, fractions included in the range (e.g., 1 to 5 may include 1, 2, 3, 4 when referring to, for example, a plurality of elements, and may also include 1.5, 2, 2.75, and 3.80 when referring to, for example, a measurement result). The recitation of endpoints also includes the recited endpoint values themselves (e.g., 1.0 to 5.0 includes both 1.0 and 5.0). Any numerical range recited herein is intended to include all subranges incorporated therein.
[0110] The term "conversion" refers to the mole fraction (ie, percentage) of a reactant that is converted to one or more products. The term "selectivity" refers to the percentage of a reactant that is converted to a specified product.
[0111] The terms "wt %, "volume %" or "mole %" refer to the weight, volume or mole percentage of a component, respectively, based on the total weight, total volume or total moles of the material including the component. In a non-limiting example, 10 grams of a component in 100 grams of a material is 10% by weight of the component.
[0112] The term "naphtha" refers to the general definition used in the oil and gas industry. In particular, it refers to hydrocarbons derived from crude oil distillation having a boiling range of 15 to 250° C. when measured by ASTM D2887-22e1. Naphtha is substantially free of olefins because the hydrocarbons are derived from crude oil. Naphtha is generally considered to have a carbon number between C3 and C11, although in some cases the carbon number can reach C15. It is also generally recognized that the density of naphtha ranges from 0.65 to 0.77 g / mL.
[0113] The term "gas oil" refers to the general definition used in the oil and gas industry. In particular, it refers to hydrocarbons having a boiling point in the range of 250 to 350° C. when measured according to ASTM D7500-15 (2019).
[0114] The term "liquefied waste polymer" refers to any hydrocarbon liquid obtained from waste polymers, preferably obtained from waste plastics. In order to obtain such liquefied waste polymers, processes such as hydrothermal liquefaction or thermal pyrolysis or catalytic pyrolysis or steam pyrolysis or even pyrolysis in the presence of hydrogen can be used. Any polymer considered as waste is encompassed by the waste polymer, such as discarded polyethylene (PE), discarded polypropylene (PP), discarded polyethylene terephthalate (PET), discarded polyvinyl chloride (PVC), and other polymers such as those derived from discarded or used tires. The term "liquefied waste polymer" also encompasses "pyrolysis plastic oil".
[0115] The term "pyrolysis plastic oil" refers to the liquid product obtained once the discarded plastic has been thermally pyrolyzed. The pyrolysis process should be understood as a non-selective thermal cracking process. Pyrolysis involves breaking the polymer chain by heating. Pyrolysis does not decompose the polymer into its original monomers, but tends to produce a series of shorter chain compounds, which are similar to the mixture of hydrocarbons found in crude oil and oil products in many aspects. Catalysts are sometimes used to reduce the operating temperature. The pyrolyzed plastic can be of any type. For example, the pyrolyzed plastic can be polyethylene, polypropylene, polystyrene, polyester, polyamide, polycarbonate, etc. These liquefied waste polymers contain paraffin, iso-paraffin (isomeric-paraffin), diene, alkyne, olefin, cycloalkane and aromatic components. The liquefied waste polymer may also contain impurities such as organic chlorides, organosilicon compounds, metals, salts, oxygen-containing compounds, sulfur and nitrogen compounds, etc. The source of plastic is discarded plastic, without restrictions on the source of plastic or on the properties. The composition of the liquefied waste polymer depends on the type of pyrolyzed plastic. However, it is mainly composed of impurities and hydrocarbons having 1 to 50 carbon atoms.
[0116] The contents of paraffins, cycloparaffins, olefins and aromatics were determined according to the standardized method UOP990-11. This method uses two-dimensional gas chromatography (GCxGC) coupled to a flame ionization detector (FID).
[0117] The term diene value (DV) or maleic anhydride value (MAV) corresponds to the amount of maleic anhydride (expressed as iodine equivalents) that will react with 100 parts of oil under specific conditions. It is a measure of the conjugated double bonds in the oil. 1 mole of maleic anhydride corresponds to 1 conjugated double bond. A known method for quantifying dienes is UOP 326-17: Diene value by maleic anhydride addition reaction. The term diene value (DV) refers to an analytical method by titration, expressed in g iodine / 100 g sample. The term maleic anhydride value (MAV) refers to an analytical method by titration, expressed in mg maleic acid / g sample. There is a correlation between MAV=DV*3,863, since 2 moles of iodine correspond to 1 mole of maleic anhydride. For the examples presented, a specific method was used. The weight % of dienes presented in this application are obtained according to this specific method described in the Examples section.
[0118] The term bromine number corresponds to the amount of bromine in grams reacted by 100 grams of a sample. This value indicates the amount of olefins in the sample. It is measured in grams of Br2 / per 100 grams of solution (gBr2 / 100g) and can be measured, for example, according to method D1159-07 (2017).
[0119] The term bromine index is the number of milligrams of bromine that react with 100 grams of a sample. It is measured in milligrams of Br2 / per 100 grams of solution (mgBr2 / 100g) and can be measured, for example, according to method ASTM D2710-20.
[0120] The term boiling point used refers to the boiling point generally used in the oil and gas industry. They are measured at atmospheric pressure. The initial boiling point is defined as the temperature value when the first bubble of steam is formed. The final boiling point is the highest temperature that can be reached during a standard distillation. At this temperature, no more steam can be driven into the condensation unit. The determination of the initial boiling point and the final boiling point is known per se in the art. Depending on the boiling range of the mixture, they can be determined using various standardized methods, such as ASTM D2887-22e1, which relates to the boiling range distribution of petroleum fractions by gas chromatography. For compositions containing heavier hydrocarbons, ASTM D7169-20e1 can be used alternatively. The boiling range of the distillate can also be advantageously measured using ASTM D7500-15 (2019) or standard NF EN 15199-1. Due to the nature of the liquefied waste polymers, the preferred method for the measurement of the boiling point is method NF EN 15199-1. Depending on the method, differences of up to 10°C can be demonstrated. Therefore, the boiling points stated here should be considered with an absolute uncertainty of + / - 10°C.
[0121] Molecular weight: Mn (number average molecular weight), Mw (weight average molecular weight), Mz (z average molecular weight), and molecular weight distribution d (Mw / Mn) and d' (Mz / Mw) are determined by gel permeation chromatography (GPC). GPC is performed as follows.
[0122] Equipment: Agilent 1260 Series Degasser (Part No. G1322A); Agilent 1260 Series Isocratic Pump (Part No. G1310B); Agilent 1260 Series Autosampler (Part No. G1329B); Agilent 1260 Series Thermostatic Column Compartment (Part No. G1316A); Agilent 1260 Series Multi-Wavelength Detector (Part No. G1365C); and Agilent 1260 Series Refractive Index Detector (Part No. G1362A).
[0123] Column set: 1x Agilent ResiPore 50x4.6mm guard column (Part No. PL1513-1300); and 2x Agilent ResiPore 250x4.6mm 3um particle size columns (Part No. PL1513-5300).
[0124] Software: Cirrus 3.3, ChemStation B04.03
[52] .
[0125] Solvent: THF stabilized with 250ppm BHT
[0126] Flow rate: 0.45 ml / min.
[0127] Column chamber temperature: 40°C
[0128] Injection volume: 5ml
[0129] Sample preparation: Weigh approximately 0.06 grams of sample into a bottle. Dissolve in 10 ml THF and filter through a 0.45 micron PTFE membrane. Run the sample on the day of sample preparation.
[0130] Polystyrene calibration standards were used.
[0131] The molecular weight average used in establishing molecular weight / property relationships is the number average molecular weight (M n ), weight average molecular weight (M w ) and z-average molecular weight (M z ). These averages are defined by the following expressions and are calculated by M i Determination:
[0132]
[0133] Here N i and W i are the number and weight of molecules with molecular weight Mi, respectively.
[0134] The molecular weight distribution (MWD) was then calculated as Mw / Mn.
[0135] Crystallization temperature (Tc) and glass transition temperature (Tg) were measured using differential scanning calorimetry (DSC), TA Instruments Q2000 equipped with a liquid nitrogen cooling system (LNCS). The software was TA Instruments UniversalAnalysis 2000 version 4.5A. We used a temperature ramp with a ramp rate of 10°C / min.
[0136] As will be apparent to one skilled in the art from this disclosure, the particular features, structures, characteristics or embodiments may be combined in any suitable manner in one or more embodiments. DETAILED DESCRIPTION
[0137] It has been found that the use of Lewis acids such as Friedel-Crafts catalysts to polymerize polymerizable materials in pyrolysis oils, and in particular plastic pyrolysis oils containing dienes, results in polymerizable materials having low Tg The formation of a low molecular weight liquid resin with low viscosity and some aromatic content. Other monomers such as branched mono-olefins, vinyl-aromatic or other dienes can be combined with the pyrolysis oil to provide additional monomer feed that can be copolymerized to change the properties and compatibility and impart the desired functionality to the resin.
[0138] One aspect of the present invention is to provide a rubber composition comprising an oligomeric product or liquid resin derived from pyrolysis oil. The liquid resin comprises a homopolymer or copolymer resin based on low molecular weight pyrolysis oil obtained using a Friedel-Crafts catalyst and preferably has a low viscosity and some aromatic content.
[0139] The present invention relates to a rubber composition comprising:
[0140] a) at least one elastomer selected from synthetic elastomers and natural elastomers;
[0141] b) a curing agent; and
[0142] c) an oligomeric product prepared from liquefied waste polymer, said oligomeric product having a number average molecular weight Mn in the range of 100 to 10 000 g / mol measured using gel permeation chromatography and polystyrene calibration, and wherein said oligomeric product exhibits a crystallization temperature below 35°C, or a glass transition temperature (Tg) below -20°C when determined by differential scanning calorimetry.
[0143] In some embodiments, the content of the at least one elastomer in the rubber composition ranges from 1 to 150 phr; preferably, from 1 to 120 phr; more preferably, from 1 to 100 phr; from 50 to 150 phr.
[0144] In some embodiments, the content of the curing agent in the rubber composition ranges from 0.1 to 25 phr; preferably, 0.5 to 22 phr; more preferably, 1 to 20 phr, and even more preferably, 5 to 18 phr.
[0145] In some embodiments, the content of the oligomeric product in the rubber composition ranges from 0.1 to 50 phr; preferably, from 0.5 to 40 phr; more preferably, from 1 to 30 phr, even more preferably, from 5 to 25 phr.
[0146] In a preferred embodiment, the oligomeric product is used to prepare a rubber composition. Preferably, the rubber composition comprises rubber or an elastomer. In the rubber composition, preferably 100 phr of rubber and 0.1-30 phr of the oligomeric product, 1-30 phr of a curing agent, and / or 0 to 30 phr of an auxiliary agent (coagent), or any mixture thereof, are included. Other components such as accelerators and / or activators and / or fillers and / or other additives may be added.
[0147] In some embodiments, when 1 When measured by H NMR, the oligomeric product shows an olefin content of at most 20.0 wt%. Preferably, the liquid resin has an olefin content in the range of 0.1 to 20.0 wt%; preferably 0.3 to 15.0 wt%; more preferably 0.5 to 10.0 wt%, 0.8 to 5.0 wt%.
[0148] In some embodiments, when 1 When measured by H NMR, the oligomeric product exhibits an aliphatic content ranging from 15 to 100 wt %; preferably ranging from 40.0 to 99.5 wt %; more preferably ranging from 50.0 to 99.0 wt %; even more preferably ranging from 70.0 to 98.5 wt %; and most preferably ranging from 80.0 to 98.0 wt %.
[0149] In one or more embodiments, when 1 When measured by H NMR, the oligomeric product exhibits an aromatic content in the range of 0.3 to 45.0 wt %; preferably in the range of 0.5 to 40.0 wt %; more preferably in the range of 0.8 to 30.0 wt %; and even more preferably in the range of 1.0 to 20.0 wt %.
[0150] In an embodiment, the oligomeric product has a viscosity measured at 30°C using a Brookfield viscometer ranging from 10 to 50,000 cps; preferably ranging from 10 to 50,000 cps; more preferably ranging from 10 to 10,000 cps; even more preferably ranging from 10 to 4000 cps; and most preferably ranging from 10 to 2500 cps.
[0151] In some embodiments, the oligomeric product has a number average molecular weight (Mn) in the range of 100 to 10,000 g / mol; preferably 120 to 5,000 g / mol; more preferably 140 to 1,000 g / mol; even more preferably 150 to 800 g / mol; most preferably 180 to 700 g / mol; or 200 to 650 g / mol; or 250 to 550 g / mol as measured using gel permeation chromatography and polystyrene calibration.
[0152] In some embodiments, the oligomeric product has a weight average molecular weight (Mw) ranging from 100 to 10,000 g / mol; preferably 120 to 5,000 g / mol; more preferably 150 to 3,500 g / mol; and even more preferably 200 to 2,000 g / mol as measured using gel permeation chromatography and polystyrene calibration.
[0153] In some embodiments, the oligomeric product has a z-average molecular weight (Mz) ranging from 100 to 100,000 g / mol; preferably 120 to 85,000 g / mol; more preferably 150 to 70,000 g / mol; and even more preferably 200 to 50,000 g / mol as measured using gel permeation chromatography and polystyrene calibration.
[0154] In some embodiments, the oligomeric product has a Mw / Mn ranging from 1.0 to 10.0; preferably 1.0 to 5.0; more preferably 1.0 to 4.0; and even more preferably 1.1 to 2.8.
[0155] In a preferred embodiment, the oligomeric product comprises a comonomer selected from the group consisting of styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-tert-butylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2,4-diisopropylstyrene, 2,4,6-trimethylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, 1-vinylnaphthalene, 2-vinylnaphthalene, vinylanthracene, 4-methoxystyrene, monochlorostyrene, dichlorostyrene, divinylbenzene, indene, methyl-indene, and mixtures thereof; preferably, the liquid resin (i.e., the oligomeric product) comprises a comonomer, and the comonomer is or comprises styrene.
[0156] In an embodiment, the oligomeric product comprises the comonomer present in a concentration ranging from 0.01 to 90 mol %, preferably 1.0 to 80 mol %, based on the total weight of the liquid resin.
[0157] In some embodiments, the oligomeric product is a wax and / or exhibits a crystallization temperature (Tc) below 35°C; preferably in the range of 18 to 32°C; more preferably in the range of 20 to 30°C; and even more preferably in the range of 21 to 29°C.
[0158] In an embodiment, the oligomeric product is a resin and / or exhibits a glass transition temperature (Tg) of below -20°C; preferably in the range of -60°C to -25°C; more preferably -50°C to -30°C; and even more preferably -49°C to -35°C when measured by differential scanning calorimetry.
[0159] The present disclosure also provides a process and apparatus for preparing a rubber composition comprising the production of the oligomeric product. Figure 1 and the device Figure 5 The apparatus and process are described together herein.
[0160] The process for preparing the rubber composition comprises the following steps:
[0161] a) providing a feed stream 1 containing liquefied waste polymer, wherein the feed stream 1 contains at least 0.1 wt. % to at most 80 wt. % of dienes, based on the total weight of the feed stream 1;
[0162] c) subjecting the feed stream 1 to a polymerization reaction under polymerization conditions to obtain a first product stream 3 comprising oligomeric products;
[0163] d) optionally, conducting a neutralization reaction by contacting the first product stream 3 with a basic compound to obtain a neutralized product stream 4, and removing the basic compound from the neutralized product stream 4 to obtain a second product stream 5;
[0164] g) separating the oligomeric products from the purified liquefied waste polymer; and
[0165] h) preparing a rubber composition comprising: at least one elastomer selected from synthetic elastomers and natural elastomers; a curing agent; and the oligomeric product recovered in step g).
[0166] exist Figure 1 In the preferred embodiment shown in , the process for preparing the rubber composition comprises the following steps:
[0167] a) providing a feed stream 1 containing liquefied waste polymer, wherein the feed stream 1 contains at least 0.1 wt. % to at most 80 wt. % of dienes, based on the total weight of the feed stream 1;
[0168] b) optionally, drying feed stream 1 to obtain a dried feed stream 2;
[0169] c) subjecting the feed stream 1 or the dried feed stream 2 to polymerization under polymerization conditions to obtain a first product stream 3 comprising oligomeric products;
[0170] d) optionally, conducting a neutralization reaction by contacting the first product stream 3 with a basic compound to obtain a neutralized product stream 4, and removing the basic compound from the neutralized product stream 4 to obtain a second product stream 5;
[0171] e) optionally, washing the first product stream 3 or the second product stream 5 with a solvent to obtain a washed stream 6;
[0172] f) optionally, filtering the stream obtained in the previous step to obtain a filtered stream 7, wherein the filtration is carried out to remove solids from the first product stream or from the second product stream 5 or from the washed stream 6, and / or to agglomerate remaining traces of solvent, if any;
[0173] g) separating to separate the oligomeric product from the purified liquefied waste polymer; and
[0174] h) preparing a rubber composition comprising: at least one elastomer selected from synthetic elastomers and natural elastomers; a curing agent; and the oligomeric product recovered in step g).
[0175] In a preferred embodiment, the process for preparing the rubber composition comprises the following steps:
[0176] a) providing a feed stream 1 containing liquefied waste polymer, wherein the feed stream 1 contains at least 0.1 wt. % to at most 80 wt. % of dienes, based on the total weight of the feed stream 1;
[0177] b) drying feed stream 1 to obtain a dried feed stream 2;
[0178] c) subjecting the dried feed stream 2 to a cationic polymerization reaction under polymerization conditions to obtain a first product stream 3 comprising oligomeric products;
[0179] d) performing a neutralization reaction by contacting the first product stream 3 with a basic compound to obtain a neutralized product stream 4, and removing the basic compound from the neutralized product stream 4 to obtain a second product stream 5;
[0180] e) washing the second product stream 5 with a solvent to obtain a washed stream 6;
[0181] f) filtering the washed stream 6 to obtain a filtered stream 7, wherein the filtering is performed to remove solids from the washed stream 6 and / or to agglomerate remaining traces of solvent, if any;
[0182] g) separating to separate the oligomeric product from the purified liquefied waste polymer; and
[0183] h) preparing a rubber composition comprising: at least one elastomer selected from synthetic elastomers and natural elastomers; a curing agent; and the oligomeric product recovered in step g).
[0184] The present disclosure also provides an apparatus 100 for carrying out a process for preparing a rubber composition, said apparatus being notable in that it comprises:
[0185] - a polymerization section C comprising one or more polymerization reactors 23;
[0186] - an optional neutralizing part D;
[0187] - a separation section comprising a separation unit 32 comprising one or more distillation columns,
[0188] wherein the polymerisation section C and the separation section are fluidly connected in series, and wherein the neutralisation section D (when present) is located downstream of said polymerisation section and upstream of said separation section.
[0189] In some embodiments, the present disclosure also provides an apparatus 100 for carrying out a process for preparing a rubber composition, the apparatus being notable in that it comprises:
[0190] - optional pretreatment part A;
[0191] - an optional drying part B;
[0192] - a polymerization section C comprising one or more polymerization reactors 23;
[0193] - an optional neutralizing part D;
[0194] - an optional washing part E;
[0195] - an optional filtration section; and
[0196] - A separation section comprising a separation unit 32 comprising one or more distillation columns.
[0197] In an embodiment, the present disclosure also provides an apparatus 100 for carrying out a process for preparing a rubber composition, the apparatus being notable in that it comprises:
[0198] - a pretreatment section A comprising a pyrolysis unit 11, one or more separation units (13, 16, 19) and optionally a washing unit 18;
[0199] - Drying section B, which comprises a decanter and / or a centrifuge 21; and / or a molecular sieve 22;
[0200] - a polymerization section C comprising one or more polymerization reactors 23; preferably loaded with an acidic catalyst;
[0201] - a neutralization section D, a mixing reactor 24 and an optional separation unit 26 comprising at least one selected from a decanter, a centrifuge and a filter;
[0202] - a washing section E comprising a mixing vessel 28 and a separation unit 30, comprising a decanter and / or a centrifuge;
[0203] - a filtration section comprising a filter and optionally a molecular sieve 31; and
[0204] - A separation section comprising a separation unit 32 comprising one or more distillation columns.
[0205] Feed stream 1 and step a) of providing feed stream 1 and pretreatment section A
[0206] The feed stream 1 used in the process contains liquefied waste polymer.
[0207] Preferably, the liquefied waste polymer is derived from pyrolysis of plastic waste 10, so that the liquefied waste polymer is pyrolysis plastic oil.
[0208] Therefore, in a preferred embodiment, step a) of providing the feed stream 1 comprises a preliminary step of preparing a liquefied waste polymer, said preliminary step comprising:
[0209] a1) providing a waste stream 10, which is preferably a waste plastic stream;
[0210] a2) pyrolyzing the waste stream 10 at a temperature of at least 200° C.;
[0211] a3) collecting a pyrolyzer effluent 12 and separating the pyrolyzer effluent into a C1 to C4 hydrocarbon fraction 14, a fraction 17 having a boiling range above 350° C., and a remaining fraction as the pyrolyzed plastic oil;
[0212] In such a case, the apparatus 100 may comprise a pretreatment section A comprising a pyrolysis unit 11, one or more separation units (13, 16, 19) and an optional washing unit 18. Preferably, the pretreatment section A comprises one or more separation units selected from the following:
[0213] - A first separation unit 13, which is used to remove pyrolysis gases, including a gas-liquid separator
[0214] a second separation unit 16 for removing the fraction having a boiling range above 350° C., comprising one or more distillation columns; and
[0215] - A third separation unit 19 for removing particles and colloids, comprising a filter and / or a centrifuge.
[0216] In some embodiments (not shown), the process further comprises a further preliminary step of treating the fraction with a boiling range above 350°C, and therefore further comprises a step a4): sending the fraction with a boiling range above 350°C to a fluid catalytic cracking (FCC) unit, or a hydrocracking unit, a coker, or a visbreaker; or blending the fraction with a boiling range above 350°C in crude oil or in a crude oil fraction for further refining.
[0217] In a preferred embodiment, the liquefied waste plastic mainly contains pyrolysis plastic oil. Pyrolysis plastic oil is produced by pyrolysis of plastic waste. Examples of pyrolysis processes for waste plastics are disclosed in US 8,895,790 or in US2014 / 228606 and in WO2016 / 009,333.
[0218] In the waste plastic pyrolyzer, mixed plastics (e.g., waste plastics 10) are placed in a pyrolysis unit or pyrolyzer. In the pyrolysis unit 11, the waste plastics are converted into pyrolysis products via pyrolysis, wherein the pyrolysis products 12 contain a gas phase (e.g., pyrolysis gas, mainly such as C1 to C4 gas, hydrogen (H 2 ), carbon monoxide (CO), carbon dioxide (CO 2 )) and a liquid phase, wherein the liquid phase is pyrolysis plastic oil.
[0219] Plastic waste 10 may include post-consumer waste plastics, such as mixed plastic waste. Mixed plastics may include non-chlorinated plastics (e.g., polyolefins, polyethylene, polypropylene, polystyrene, copolymers, etc.), chlorinated plastics (e.g., polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), etc.), etc., or mixtures thereof. Generally, waste plastics 10 include long-chain molecules or polymer hydrocarbons. Waste tires may also be used. That is, waste plastics may also include used tires.
[0220] The pyrolysis unit 11 can be any suitable container configured to convert waste plastic into gas and liquid products (e.g., simultaneously). The container can be configured for gas phase, liquid phase, vapor-liquid phase, gas-solid phase, liquid-solid phase, or slurry phase operation.
[0221] The container may contain one or more beds of an inert material or a pyrolysis catalyst, including sand, zeolite, alumina, a catalytic cracking catalyst, or a combination thereof. Generally, the pyrolysis catalyst is capable of transferring heat to the components undergoing the pyrolysis process in the pyrolysis unit. Alternatively, the pyrolysis unit 11 may be operated without any catalyst (e.g., pure thermal pyrolysis).
[0222] The pyrolysis unit 11 can be operated in an adiabatic, isothermal, non-adiabatic, non-isothermal, or a combination thereof. The pyrolysis reaction of the present disclosure can be carried out in a single stage or in multiple stages. For example, the pyrolysis unit 11 can be two reactor vessels connected in series fluidly.
[0223] In a configuration (not shown) in which the pyrolysis unit includes two containers, the pyrolysis process can be divided into a first stage performed in a first container and a second stage performed in a second container and fluidly connected downstream of the first stage. As will be appreciated by those skilled in the art, and with the help of the present disclosure, the second stage can enhance the pyrolysis of the intermediate pyrolysis product stream flowing from the first stage into the second stage to obtain pyrolysis products flowing out of the second stage. In some configurations, the first stage can utilize thermal cracking of the waste plastic, and the second stage can utilize thermal cracking or catalytic cracking of the waste plastic to obtain pyrolysis products flowing out of the second stage. Alternatively, the first stage can utilize catalytic cracking of the waste plastic, and the second stage can utilize thermal cracking or catalytic cracking of the waste plastic to obtain pyrolysis products flowing out of the second stage.
[0224] In some configurations, the pyrolysis unit 11 may include one or more devices configured to convert the mixed plastic into gas and liquid products. The one or more devices may or may not contain inert materials or pyrolysis catalysts as described above. Examples of such devices include one or more of the following: a heated extruder, a heated rotary kiln, a heated tank reactor, a packed bed reactor, a bubbling fluidized bed reactor, a circulating fluidized bed reactor, an empty heated container, a closed heated surface where the plastic flows down the wall and cracks, a container surrounded by an oven or kiln, or any other suitable device that provides a heated surface to assist in cracking.
[0225] The pyrolysis unit 11 can be configured to perform pyrolysis (e.g., cracking), and in some aspects (e.g., where hydrogen is added to the pyrolysis unit), additionally hydrogenate components of the waste plastic stream fed to the pyrolysis unit. Examples of reactions that can occur in the pyrolysis unit 11 include, but are not limited to, isomerizing one or more normal paraffins to one or more iso-paraffins, selectively ring-opening one or more cycloparaffins to one or more iso-paraffins, cracking long chain length molecules to short chain length molecules, removing heteroatoms from hydrocarbons containing heteroatoms (e.g., dechlorination), hydrogenating coke generated in the process, or a combination thereof.
[0226] In one or more configurations of the pyrolysis unit 11, the headspace purge gas may be used in all or part of the pyrolysis stage (converting the waste plastic into liquid and / or gas phase products) to enhance cracking of the plastic, produce valuable products, provide feed for steam cracking, or a combination thereof. The headspace purge gas may include hydrogen (H2), C1 to C4 hydrocarbon gases (e.g., alkanes, methane, ethane, propane, butane, isobutane), inert gases (e.g., nitrogen (N 2 ), argon, helium, steam), etc., or a combination thereof. When the waste plastics include chlorinated plastics, the use of a headspace purge gas assists in the dechlorination in the pyrolysis unit. The headspace purge gas can be introduced into the pyrolysis unit to help remove volatiles entrained in the molten mixed plastics present in the pyrolysis unit.
[0227] The hydrogen (H 2 ) is added to the pyrolysis unit 11 to enrich the pyrolysis unit environment with H 2 , assisting in stripping of entrained hydrogen chloride in the pyrolysis unit, providing a local environment rich in hydrogen in the pyrolysis melt or liquid, or a combination thereof; for example, independently of the waste plastic 10 stream, via a stream containing H 2 The stream is fed directly to the pyrolysis unit 11. In some aspects, H 2 Introduced into the pyrolysis unit 11 together with the flow.
[0228] The pyrolysis unit 11 can promote any reaction of the components of the waste plastic 10 stream in the presence of or with hydrogen. Reactions that can occur are such as the addition of hydrogen atoms to double bonds of unsaturated molecules (e.g., olefins), resulting in saturated molecules (e.g., paraffins, iso-paraffins, cycloalkanes). Additionally, or alternatively, the reactions in the pyrolysis unit can cause the breaking of bonds of organic compounds, with subsequent reactions and / or replacement of heteroatoms with hydrogen.
[0229] The use of hydrogen in the pyrolysis unit 11 can have the following beneficial effects: (I) reducing coke as a result of cracking, (II) maintaining the catalyst (if any) used in the process in an active state, (III) improving the removal of chlorides from the stream so that the pyrolysis products from the pyrolysis unit 11 are substantially dechlorinated relative to the waste plastic stream, which minimizes the chloride removal requirements in units downstream of the pyrolysis unit, (IV) hydrogenation of olefins, (V) reducing dienes in the pyrolysis products, (VI) helping to operate the pyrolysis unit 11 at a reduced temperature to achieve the same conversion level of the waste plastic 10 stream in the pyrolysis unit, or a combination of (I)-(VI).
[0230] The pyrolysis process in the pyrolysis unit 11 may be low-severity or high-severity.
[0231] The low-severity pyrolysis process can occur at a temperature of less than about 450°C; for example, at a temperature ranging from 250°C to 450°C, preferably 275°C to 425°C, more preferably 300°C to 400°C, and can produce a pyrolysis oil rich in mono- and di-olefins and significant amounts of aromatics.
[0232] The high-severity pyrolysis process can occur at a temperature equal to or greater than about 450°C; for example, at a temperature ranging from 450°C to 750°C, preferably 500°C to 700°C, and more preferably 550°C to 650°C, and can produce aromatic-rich pyrolysis oil and more gaseous products (compared to low-severity pyrolysis).
[0233] As will be appreciated by those skilled in the art, a high severity pyrolysis process will result in the formation of more olefins and diolefins. These olefins and diolefins cannot be easily recovered.
[0234] The pyrolysis product 12 can be collected as an effluent from the pyrolysis unit 11 and conveyed (e.g., flowed, e.g., via pumping, gravity, pressure difference, etc.) to a pyrolysis separation unit (i.e., a first separation unit 13). The pyrolysis product 12 can be separated in the pyrolysis separation unit into a pyrolysis gas 14 stream and a pyrolysis plastic oil further used in step a) of the present disclosure.
[0235] The first separation unit 13 may include any suitable gas-liquid separator, such as a steam-liquid separator, an oil-gas separator, a gas-liquid separator, a degasser, a scrubber, a collector, a flash drum, a compressor suction drum, a gravity separator, a centrifugal separator, a filter blade separator, a demister pad, a liquid-gas coalescer, a distillation tower, etc., or a combination thereof.
[0236] In a preferred embodiment, the pyrolyzed plastic oil is derived directly from the pyrolysis of plastic waste without further chemical conversion or separation.
[0237] In a preferred embodiment, the feed stream 1 contains only liquefied waste polymers, even more preferably only pyrolyzed plastic oils. Alternatively, the feed stream 1 contains at least 10% by weight; preferably at least 25% by weight, more preferably at least 50% by weight, even more preferably at least 75% by weight of liquefied waste polymers, based on the total weight of the feed stream 1.
[0238] The feed stream 1 may contain 100 wt%; preferably up to 95 wt%; more preferably up to 90 wt%; even more preferably up to 85 wt%, and most preferably up to 80 wt% of the liquefied waste polymer, based on the total weight of the feed stream 1. When the feed stream 1 contains less than 100 wt% of the liquid waste polymer, the remainder may be, for example, diluent or other hydrocarbons.
[0239] In a preferred embodiment, feed stream 1 exhibits at most 150 g Br when measured according to ASTM D1159-07 (2017). 2 / 100g, preferably up to 100g Br 2 / 100g; more preferably at most 80g Br 2 / 100 g, and even more preferably at most 50 g Br 2 Bromine value of / 100g.
[0240] In a preferred embodiment, the liquefied waste polymer in feed stream 1 has a starting boiling point of at least 15° C. and a final boiling point of at most 700° C. Preferably, the final boiling point is at most 600° C.; more preferably 560° C., even more preferably 450° C., even more preferably 350° C., most preferably 250° C.
[0241] In some embodiments, step a) of providing feed stream 1 comprises one or more sub-steps of pre-treatment of the liquefied waste polymer.
[0242] In fact, depending on the source of the liquefied waste polymer, some pretreatment may be necessary. That is, before purifying the liquefied waste polymer in the process of the present invention, the following pretreatment of the liquefied waste polymer or feed stream 1 may be considered.
[0243] In a preferred embodiment, the liquefied waste polymer or feed stream 1 is pre-treated in a washing or desalting unit 18 to remove water soluble salts prior to treatment in the process of the present invention.
[0244] In another preferred embodiment, the liquefied waste polymer or stream 1 is pre-treated in a separation unit 19 to extract particles and colloids 20 by filtration, centrifugation or a combination of both techniques before being treated in the process of the present invention.
[0245] Optional step b) of drying feed stream 1 to obtain dried feed stream 2 and drying part B
[0246] In another preferred embodiment, the liquefied waste polymer or feed stream 1 is pretreated in a dehydration unit (i.e., a drying unit) before being treated in the process of the present invention to remove water from the hydrocarbon stream to reach a water content of less than 0.1% by volume, preferably less than 0.05% by volume according to ASTM D95-13 (2018), and even more preferably the liquefied waste polymer can be decanted.
[0247] Preferably, the feed stream 1 is dried before being sent to the polymerization unit. Step b) of drying may be followed by a sub-step b1) of decantation and / or centrifugation; preferably, sub-step b1) is followed by a sub-step b2) of drying using a molecular sieve 22 to reach a water content of less than 0.1% by volume according to ASTM D95-13 (2018).
[0248] In such a case, the apparatus 100 may include a drying section B comprising:
[0249] - a decanter and / or a centrifuge 21; and / or
[0250] -Molecular sieve 22
[0251] Step c) of subjecting feed stream 1 or dried feed stream 2 to polymerization and polymerization part C
[0252] Step c) comprises carrying out a polymerization reaction, which is a cationic polymerization, a free radical polymerization or an anionic polymerization; preferably, the polymerization reaction is a cationic polymerization. Therefore, the polymerization part C comprises one or more polymerization reactors 23 loaded with a catalyst; preferably an acidic catalyst.
[0253] In an embodiment, the polymerization is an anionic polymerization. In such a case, the anionic polymerization is carried out using an anionic initiator containing an organolithium and is terminated by reaction with a selected proton donor terminator to form a filterable lithium salt.
[0254] In the embodiment where the polymerization reaction is a cationic polymerization, the apparatus comprises a polymerization section C comprising one or more polymerization reactors 23 loaded with an acidic catalyst.
[0255] In another embodiment, the polymerization is a free radical polymerization. In such a case, the free radical polymerization is carried out with an initiator, which is used to generate the initial free radicals that lead to monomer propagation, followed by termination via combination or disproportionation.
[0256] In a preferred embodiment, the polymerization reaction is a cationic polymerization. Therefore, preferably, step c) is carried out in the presence of an acidic catalyst; preferably, the acidic catalyst is a Bronsted acid or a Lewis acid; preferably a Lewis acid in the form of a transition metal halide.
[0257] Friedel-Crafts catalysts are strong Lewis acid catalysts that polymerize monomers via a cationic polymerization mechanism. According to various embodiments of the present invention, examples of Friedel-Crafts catalysts that can be used to polymerize monomer feeds containing pyrolysis oil include, but are not limited to, boron trifluoride, aluminum chloride, tin tetrachloride, titanium trichloride, titanium tetrachloride, iron (III) chloride, aluminum tribromide, dichloromonoethylaluminum, and complexes thereof, such as boron trifluoride-phenol complexes, boron trifluoride-ethanol complexes, boron trifluoride-ether complexes, etc., especially boron trifluoride-phenol complexes and boron trifluoride-ethanol complexes. Friedel-Crafts catalysts may also include liquid aluminum chloride / hydrochloric acid / substituted aromatic complexes, the aromatics being, for example, o-xylene, mesitylene, ethylbenzene, isopropylbenzene, etc., such as short-chain or long-chain alkylbenzenes. The alkyl chain may be linear or branched, and may vary from 2 to 30 carbon atoms. Acidic liquid AICI, obtained as a by-product during the alkylation of benzene or any other substituted aromatic (toluene, xylene) with branched olefins, can also be used. Branched olefins can be produced via boron trifluoride oligomerization and fractionation of propylene (e.g., C 12 Olefins or C 24 Olefins can be alkylated with aromatics).
[0258] The most preferred Friedel-Crafts catalyst is AlCl 3 and BF 3 .
[0259] Therefore, preferably, step c) is carried out in the presence of an acidic catalyst, wherein the acidic catalyst is a Lewis acid selected from BF 3 , boron trifluoride complex, AICl 3 SnCl 4 、ZnCl 2 、FeCl 3 and TiCl 3 , alkylaluminum chloride, H 2 SO 4 , or any mixture thereof. Understand, BF 3 Refers to BF in gaseous form 3 A particularly suitable complex of boron trifluoride is boron trifluoride etherate.
[0260] In an embodiment, step c) is performed in the presence of an acidic catalyst, the acidic catalyst being a Lewis acid, wherein the acidic catalyst concentration ranges from 0.5 wt % to 5.0 wt %, based on the total weight of the feed stream 1 .
[0261] In an embodiment, the reaction conditions include a contact time of at least 5 minutes to at most 5 hours. Preferably, step c) is carried out under an inert atmosphere, preferably N 2 Carried out in atmosphere.
[0262] The resins described herein can be prepared by a continuous solution polymerization process, wherein a Friedel-Crafts catalyst, optional comonomers, and a suitable aromatic or aliphatic hydrocarbon solvent, such as toluene, xylene, or heptane, are continuously added to a reactor vessel to form the desired homopolymer or copolymer. Alternatively, pyrolysis oil-based polymers can be prepared by a batch process, wherein all initiators, monomers, and solvents are combined together and mixed in a reactor. The acidic catalyst may also be a solid catalyst.
[0263] Preferably, during the continuous polymerization reaction, the mass flow rate of the catalyst feed is 0.01 to 20 wt %; preferably 0.1 to 5 wt %, and more preferably 0.1 to 3 wt %, based on the total mass flow rate of the monomer feed and the catalyst feed.
[0264] The reaction temperature of the mixture in the reactor vessel is also preferably maintained at about -10 to 50°C (when BF is used as the Friedel-Crafts catalyst) and about 10 to 60°C (when AlCl is used). 3 at a temperature of 1 hr.
[0265] The low molecular weight pyrolysis oil based homopolymer or copolymer resin according to an embodiment of the present invention is a liquid resin having a number average molecular weight between 100 and 10,000 g / mol and more preferably 250 and 4,000 g / mol when measured via gel permeation chromatography and converted using polystyrene calibration.
[0266] In a preferred embodiment, the cationic polymerization is carried out in the presence of an acidic catalyst, which is preferably selected from BF 3 、AlCl 3 SnCl 4 and TiCl 3 , ion exchange resin, Cl 2 AlEt、H 2 SO 4 , or any mixture thereof.
[0267] In an embodiment, AlCl 3 and BF 3 At least one of the polymerization initiator and the polymerization initiator can be used to polymerize a monomer feed comprising pyrolysis oil and a comonomer, wherein the comonomer content of the monomer feed is <90 wt%, <40 wt%, <25 wt%, or <15 wt%, based on the total moles of monomers in the monomer feed. Preferably, the polymerization initiator is BF 3 .
[0268] In particular, the acidic catalyst may be a solid acidic catalyst. Preferred solid acidic catalysts include molecular sieves, such as zeolites or silicalite. The use of solid acidic catalysts is particularly advantageous. The solid acidic catalyst can be easily separated. When a solid acidic catalyst is used, the neutralization step d) and the washing step e) may not be required.
[0269] In an embodiment, step c) is carried out when the solid acid catalyst is a molecular sieve, preferably selected from the topological MFI, BEA, FAU, MEL, and the polymerization conditions include a range of 0.5 to 5.0 h -1 In a preferred embodiment, the molecular sieve contains one or more heteroatoms selected from Ti, Sn, Mo, W, Fe, Ni, Co, Cu, Zr, Hf, Nb and Ta.
[0270] In an embodiment, step c) is carried out with the solid acid catalyst being an ion exchange resin, preferably a sulfonic acid ion exchange resin such as Amberlyst A15 or A35, and the polymerization conditions include a range of 0.5 to 5.0 h -1 The ion exchange resin includes an acidic resin such as a + In a preferred embodiment, the ion exchange resin is Amberlyst 15.
[0271] In an embodiment, step c) is carried out when the solid acid catalyst is clay or activated clay, and the polymerization conditions include a range of 0.5 to 5.0 h -1 LHSV.
[0272] Optional neutralization step d) and neutralization part D
[0273] When a soluble acidic catalyst is used in step c) to produce the first product stream 3, it may need to be subjected to a neutralization step d1), preferably followed by a washing step d2).
[0274] Thus, in some embodiments, the apparatus 100 comprises a neutralization section D comprising a mixing reactor 24 and an optional separation unit 26 comprising at least one selected from a decanter, a centrifuge, and a filter.
[0275] Step d) is a neutralization step, which can be accomplished by adding a base directly to the first product stream 3. In such a case, a basic compound, generally a solid, is brought into contact with the first product stream 3, and the obtained mixture is then stirred for at least 1 second to at most 24 hours, preferably during at least 1 minute to at most 12 hours. After stirring, the remaining base in solid form is separated from the liquid, which is the second product stream 5.
[0276] The neutralization step can also be accomplished by washing the first product stream 3 with a basic compound 25, which is a basic solution. The basic aqueous solution is preferred and contains NaOH and / or NH 4 An alkaline aqueous solution of OH is the most preferred type of solution. The alkaline solution is contacted and agitated for at least 1 second to at most 24 hours, preferably at least 1 minute to at most 12 hours. The mixture is then separated to remove the second product stream 5 (which is an organic phase) from the aqueous phase. The separation may, for example, comprise decantation. Decantation is known per se and comprises separating the immiscible organic and aqueous phases with the aid of gravity.
[0277] The neutralization step can also be carried out by simultaneously or sequentially reacting one or more basic compounds 25, preferably a base containing an alkali metal / alkaline earth metal, more preferably a solid base such as LiOH, NaOH, CsOH, Ba(OH) 2 、Na 2 O, KOH, K 2 O, CaO, Ca(OH) 2 、MgO、Mg(OH) 2 , or any mixture thereof, or any strong base alone or in combination, and a basic aqueous solution are contacted with the first product stream 3. After agitation for at least 1 second to at most 24 hours, the solid, the organic phase which is the second product stream 5, and the aqueous phase are separated.
[0278] In a more preferred embodiment, step d) is performed in a continuous mode, i.e., addition of fresh alkaline compound is performed at, for example, the inlet of the mixing reactor 24 to the first product stream 3, while the spent alkaline compound is removed at the outlet of the mixing reactor 24 to obtain the second product stream 5.
[0279] In a preferred embodiment, the basic compound comprises an alkali metal cation, an alkaline earth metal cation and a quaternary ammonium base, preferably selected from TMAOH, TEAOH, TBAOH, TPAOH, or any mixture thereof.
[0280] Optional washing step e) and washing part E
[0281] The washing step e) comprises washing the first product stream 3 or the second product stream 5 with a solvent 27 to obtain a washed stream 6. In some embodiments, the washing step e) is performed after the neutralization step d) to remove trace amounts of basic compounds 25. In such a case, the washing step is performed with a ratio of the second product stream 5 or optionally the neutralized product stream 4 to the solvent 27 ranging from 0.05 to 20.
[0282] For example, washing is performed at a temperature ranging from 5° C. to 95° C., preferably at atmospheric pressure. Washing may be performed in a continuous mode or in a batch mode.
[0283] In a preferred embodiment, the solvent is selected from water or an acidic aqueous solution containing one or more organic acids such as citric acid (C 6 H 8 O 7 ), formic acid (CH 2 O 2 ), acetic acid (CH 3 COOH), aminosulfonic acid (H 3 NSO 3 ), or inorganic acids such as hydrochloric acid (HCl), nitric acid (HNO 3 ), sulfuric acid (H 2 SO 4 ), phosphoric acid (H 3 PO 4 ), and any combination thereof.
[0284] For example, the acidic solution has a pH ranging from 0.1 to 6.9.
[0285] Washing is preferably performed until the pH of the washed stream 6 or optionally the second product stream 5 or the neutralized product stream 4 is in the range of 5.0 to 9.0, preferably in the range of 6.0 to 8.0, even more preferably in the range of 6.5 to 7.5.
[0286] Preferably washing is followed by decantation and / or centrifugation to separate the solvent 27 from the washed mixture 29 to produce a washed stream 6 .
[0287] In such a case, the apparatus 100 may include a wash section E comprising a mixing vessel 28 and a separation unit 30, including a decanter and / or a centrifuge.
[0288] Optional filtration step f) and filtration section
[0289] The process may comprise a filtration step f) comprising filtering the stream obtained in the previous step to obtain a filtered stream 7, wherein the filtration is performed to remove solids.
[0290] In the embodiment wherein the preceding step is a washing step e), the process may comprise a filtration step f), which comprises filtering the washed stream 6 (i.e. the stream obtained in the preceding step) to obtain a filtered stream 7, wherein the filtration is performed to remove solids from the washed stream 6, and / or to agglomerate remaining traces of solvent, if any.
[0291] In a preferred embodiment, the filtration comprises a first sub-step of filtration to remove solids and / or to agglomerate remaining traces of solvent (if any), preferably followed by a second sub-step of dehydration, preferably using molecular sieves to achieve a water content of the filtered stream 7 of less than 0.1 vol.-%, preferably less than 0.05 vol.-% according to ASTM D95-13 (2018).
[0292] In such a case, the device 100 may include a filtration section including a filter (not shown) and optionally a molecular sieve 31 .
[0293] Separation step g) and separation portion
[0294] The process comprises a separation step g) to separate the oligomeric product 33 from the purified liquefied waste polymer 34 .
[0295] In a preferred embodiment, said step g) of separating is carried out via distillation or steam distillation or vacuum stripping or fractional distillation or any combination thereof.
[0296] Thus, the apparatus comprises a separation unit 32 comprising one or more distillation columns.
[0297] The oligomeric product 33 obtained can also be further used to be converted into valuable resins such as valuable resins. After the separation step g), the oligomeric product 33 can be collected and mixed with an elastomer, a curing agent and a filler to obtain a rubber composition, or used as a tackifying resin and mixed with an elastomer to form an adhesive composition.
[0298] If not already done in the pretreatment section, the process may include the step of separating and recovering a fraction having a boiling range above 350° C., preferably above 300° C. This fraction may be recovered from any one of the purified liquefied waste polymer 34, the filtered stream 7, the washed stream 6, the second product stream 5, the neutralized product stream 4, the first product stream 3, the dried feed stream, or the feed stream 1. Thus, the fraction having an initial boiling point of at least 350° C., preferably at least 300° C., may be removed and sent to an FCC unit, a hydrocracking unit, a coker, or a visbreaker, or the fraction having a boiling range above 350° C. may be blended in crude oil or in a crude oil fraction for further refining.
[0299] Preferably, after separation step g), the purified liquefied waste polymer 34 is collected and blended in a fuel pool; preferably, the purified liquefied waste polymer is separated into a naphtha fraction having a boiling range of less than 150°C and a diesel fraction having a boiling range between 150 and 350°C, wherein the naphtha fraction is incorporated into the naphtha pool and the diesel fraction is incorporated into the diesel pool.
[0300] Detailed description of the curing step
[0301] In the preparation of the rubber composition, a curable composition is prepared. The curable composition comprises rubber, the oligomeric product and at least one curing agent. The curable composition can be cured by a variety of methods, including but not limited to peroxide curing, peroxide / auxiliary agent curing, radiation curing, sulfur and thiadiazole curing.
[0302] In the present disclosure, the term "curing agent" or "curing agent" is a synonym and is interchangeable. The terms "crosslinking" and "curing" as used herein are interchangeable and are understood to mean that chemical bonds have been formed between adjacent chains of each polyene molecule. By polyene, it is meant an organic compound containing at least three alternative double carbon-carbon bonds and single carbon-carbon bonds. Examples of suitable crosslinking agents or curing agents that can be used in curable liquid rubber compositions are sulfur and peroxides. Any of these types of crosslinking agents can be used at appropriate levels with appropriate auxiliary agents, promoters or activators such as those known and used in the art to increase the speed and integrity of crosslinking. The curing agent can be selected based on the desired curing temperature of the curable composition. Typically, the curing temperature can be between 100°C and 190°C.
[0303] The curable composition comprises a rubber, the oligomeric product and at least one curing agent.
[0304] Curing agents that decompose to generate free radicals during the curing cycle may be used as curing agents in the present disclosure. Free radical generating compounds advantageously employed in the present invention may be ditertiary peroxides such as tert-butyl peroxybenzoate (TBPB).
[0305] Di-tertiary peroxide curing compounds may be used, the peroxides thereof and their homologues and analogues, all of which correspond substantially to the structural formula: R 3 COO-CR 3These di-tertiary peroxide agents contain at least one peroxide group disposed between tertiary carbon atoms connected to carbon atoms constituting the respective parts of the R groups, which may be alkyl (including linear, branched or cyclic), alkenyl or aryl groups, or mixtures of such groups, and which may be further substituted with non-hydrocarbyl groups such as ethers, additional peroxide groups or halogens such as chlorine, and the organic peroxide does not interfere with the curing process or the cured elastomer product. The R groups may be the same or different from each other.
[0306] Exemplary organic peroxides include diacetyl peroxide, dibenzoyl peroxide, dioctanoyl peroxide, di-(p-chloro-benzoyl) peroxide, didecanoyl peroxide, di-(2,4-dichlorobenzoyl) peroxide, diisobutyl peroxide, diisononanoyl peroxide, dilauroyl peroxide, dipelargonyl peroxide, dipropynyl peroxide, and dioctanyl peroxide. peroxide), di(β-carboxypropionyl) peroxide, methyl ethyl ketone peroxide, cyclohexanone peroxide, dihydroxy-dimethyl-dioxolane, tert-butyl peroxide, tert-butyl peroxide (2-ethylhexanoate), tert-butyl peroxyisobutyrate, O,O-tert-butyl-O-isopropyl monoperoxy-carbonate, tert-butyl peroxypivalate, dimethyl-di(benzoylperoxy)-hexane, tert-butyl peroxide (2-ethylbutyrate), di-tert-butyl peroxide, dicumyl peroxide, 2,5-bis(tert-butylperoxy)-2,5-dimethyl-hexane, tert-butyl hydroperoxide, cumyl hydroperoxide, α,α'-bis-(tert-butylperoxy)diisopropylbenzene, 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, and n-butyl-bis(tert-butylperoxy)-valerate, etc. Among the aforementioned free radical generating compounds, the following are commercially available and conveniently used: dicumyl peroxide (DICUP TM ), 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, di-tert-butyl peroxide (both available from AKZO Chemicals, Inc. of Chicago, Ill.), 2,5-dimethyl-2,5-di-tert-butylperoxy!-2-hexane (VAROX DBPH 50 TM )、2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne (LUPERSOL 130 TM ), tert-butyl peroxybenzoate (TBPB) and α,α'-bis-(tert-butylperoxy)-diisopropylbenzene (VULCUP R TM ). The aforementioned organic peroxides may be used alone or in combination.
[0307] Non-limiting examples of other suitable peroxides are: peroxyketals (such as 1,1'-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane or di(tert-butylperoxy)-cyclohexane); diacyl peroxides (such as dibenzoyl peroxide or dilauroyl peroxide) and peroxyesters (such as tert-butyl peroxyisobutyrate or tert-amyl peroxy-2-ethylhexyl carbonate). In another embodiment, the peroxide can be selected from peroxyketals (such as 1,1'-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane or di(tert-butylperoxy)-cyclohexane); diacyl peroxides (such as dibenzoyl peroxide) and peroxyesters.
[0308] The curable composition may include two or more organic peroxides as heat-activated crosslinking agents. For example, the curable liquid rubber composition may include at least two peroxides selected from the following: peroxyketal (such as 1,1'-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane or di(tert-butylperoxy)-cyclohexane); diacyl peroxide (such as dibenzoyl peroxide or dilauroyl peroxide) and peroxyester (such as tert-butylperoxyisobutyrate or tert-amyl-peroxy-2-ethylhexyl carbonate). "Half-life" is a convenient way to describe the rate of decomposition of an organic peroxide at a specified temperature. The time required for half of the organic peroxide originally present to decompose at any particular temperature is measured. Organic peroxides with a half-life of 10 hours from 47°C to 127°C are suitable.
[0309] The amount of peroxide present in the curable composition will vary according to the type of peroxide used, the reactivity of the curable component, the type and reactivity of the accelerator or activator (if any) and the desired cure curve and the rubber properties of the target cure and other factors. However, typically, the curable composition will comprise one or more peroxides with an amount of 1 to 30 phr (parts per hundred of butadiene homopolymer and any rubber component, if any) or 1.5 to 20 phr. It is understood that this amount only refers to peroxide. Suitable auxiliary agents can also be used except peroxide. Auxiliary agents (if any) typically exist with an amount between 0.1 and 30 phr. Auxiliary agents (if any) can exist between 0.2 and 25 phr or between 0.2 and 20 phr.
[0310] The amount of the free radical generating compound used in the present invention can vary according to the selected polymer and crosslinking aid. Therefore, the required amount of the compound generated by the free radical required for implementing the present invention is an effective amount of curing that is easily determined by a person of ordinary skill in the art. Generally, the amount of about 0.1 to about 15 parts per hundred parts of rubber.
[0311] Auxiliary agents for use in curable compositions
[0312] The curable composition may also include at least one auxiliary agent suitable for crosslinking with an organic peroxide or other free radical source. The auxiliary agent may contain one or more sites (carbon-carbon double bonds) of olefinic unsaturation per molecule, and may be selected from acrylates, methacrylates, bismaleimides, vinyl esters, allyl compounds, and derivatives thereof. In some embodiments of the present invention, the curable composition includes an auxiliary agent totaling 0phr to 30phr. In other embodiments, the composition may include 0.5 to 15phr. Non-limiting examples of suitable auxiliary agents include metallic acrylate, metallic methacrylate, metallic acrylate salt, metallic methacrylate salt. In particular, zinc acrylate, zinc methacrylate, zinc acrylate salt, and zinc methacrylate salt may be mentioned. Other metal salts of acrylic acid and methacrylic acid include, but are not limited to, magnesium, sodium, potassium, calcium, barium, cobalt, copper, aluminum, and iron.
[0313] When organic peroxides are used to crosslink the composition, sulfur may also be introduced as an auxiliary agent. When used as an auxiliary agent together with the peroxide, the sulfur content should be low, ie not more than 0.5 phr sulfur.
[0314] Sulfur in curable compositions
[0315] Sulfur can be used as a heat-activated cross-linking agent. Examples of sulfur vulcanizing agents include, but are not limited to, elemental sulfur (free sulfur) or sulfur donor vulcanizing agents, such as amine disulfide, polymeric polysulfide or sulfur olefin adducts. The amount of sulfur vulcanizing agent will vary according to the type of rubber and the specific type of sulfur vulcanizing agent, but generally ranges from about 0.1phr to about 5phr, wherein the range of about 0.5phr to about 2phr is preferred. Sulfur donors can also be used. Accelerators or activators (if any) are typically present between 0.1 and 30phr each. Accelerators or activators (if any) can be present between 0.2 and 25phr or between 0.2 and 20phr. In addition to sulfur, suitable accelerators or activators can also be used. Accelerators or activators (if any) are typically present between 0.1 and 30phr each. Accelerators or activators (if any) can be present between 0.2 and 25phr or between 0.2 and 20phr.
[0316] Sulfur donors may also be used with sulfur to reduce the sulfur content incorporated into the formulation. Non-limiting examples of sulfur donors are thiuram tetrasulfide and morpholine derivatives such as tetramethylthiuram disulfide; 4,4'-dithiodimorpholine; dipentamethylenethiuram tetrasulfide; and thiocarbamoylsulfenamide.
[0317] Accelerators in curable compositions
[0318] Examples of accelerators that can be used with sulfur as a primary curing agent include, but are not limited to, sulfenamides, thiazoles, dithiocarbamates, thiuram-based compounds of N-cyclohexyl-2-benzothiazolesulfenamide (CBS); N-tert-butyl-2-benzothiazolesulfenamide (TBBS); zinc dimethyldithiocarbamate (ZDMC), zinc dibenzyldithiocarbamate (ZBEC); 2-mercaptobenzothiazole (MBT); benzothiazole disulfide (MBTS). Some primary accelerators such as thiazoles (MBT or MBTS) or dithiocarbamates (ZDMC or ZBEC) can be used in blends with sulfenamides or in place of sulfenamides. Other non-limiting examples of accelerators are thiurams such as tetramethylthiuram disulfide (TMTD) or tetrabenzylthiuram disulfide (TBzTD). Dithiocarbamates or xanthates as mentioned above may also be employed, for example zinc isopropyl xanthate (ZIX) or sodium isopropyl xanthate (NaIX).
[0319] In the case where a combination of two or more accelerators is used, the primary accelerator may be used in an amount ranging from 0.5 to 2.0 phr and the secondary accelerator may be used in an amount ranging from about 0.1 to 0.5 phr. Combinations of accelerators are known to produce synergistic effects. Preferably, the primary accelerator is a sulfenamide. If a secondary accelerator is used, it is preferably a guanidine, dithiocarbamate, and / or thiuram compound.
[0320] Activators in curable compositions
[0321] Examples of suitable activators as primary crosslinking agents that can be used with organic peroxides or sulfur include, but are not limited to, metal oxides, fatty acid metal salts (e.g., metal stearates), fatty acids, and mixtures thereof. Non-limiting specific examples include zinc oxide, calcium oxide, magnesium oxide, zinc stearate, or stearic acid. The activator can be used in an amount ranging from about 1 to 4 phr, with a range of about 2 to 3 phr being preferred.
[0322] The cured composition can be obtained by curing the curable composition as disclosed herein by heating the curable composition. The curable composition can be cured by heating the curable composition to a temperature of about 100°C to about 240°C or a temperature of about 100°C to about 190°C. To achieve curing, the curable composition is kept at this temperature for between 5 minutes and 10 hours. As a result of such curing, the curable composition is converted (e.g., by a cross-linking reaction) into a solid elastomer (rubber-like) composition. Typically, curing is achieved by heating the curable composition to an effective temperature that induces a desired cross-linking reaction involving at least a polymer component. Typically, the time period to achieve sufficient curing is between 5 minutes and 10 hours.
[0323] Elastomer in curable composition
[0324] Suitable elastomers are those known and used in the art. For example, suitable elastomers are elastomeric organic polymers, including natural rubber and various synthetic rubbers of curing (i.e., vulcanization or crosslinking). Generally, these curable elastomers are polymers or polymers of conjugated dienes, wherein the monomers are connected by carbon-carbon bonds. Representative examples of synthetic rubbery polymers of conjugated dienes include: synthetic polyisoprene, styrene-butadiene rubber, polybutadiene rubber (different from low-viscosity butadiene homopolymers of the present invention), butyl rubber, brominated butyl rubber, chlorobutyl rubber, chloroprene rubber, ethylene propylene rubber, nitrile elastomer, silicone elastomer, thermoplastic elastomer, fluoroelastomer, high styrene butadiene copolymer, vinyl acetate ethylene copolymer, chlorinated polyethylene rubber, chlorosulfonated polyethylene elastomer, polyethylene and regenerated rubber. The functionalized forms (versions) of these elastomers may also be included in the rubber composition according to the present invention.
[0325] The curable rubber compositions used for the preparation of tires and other products according to the invention may contain a single diene elastomer or a mixture of several diene elastomers, the said diene elastomers being combined with any type of synthetic elastomer other than diene elastomers, or even with polymers other than elastomers, for example thermoplastic polymers.
[0326] Fillers in curable compositions
[0327] Representative reinforcing fillers may range from about 5 to 100 parts by weight included in the rubber composition according to various embodiments of the present invention, based on 100 parts by weight of total rubber (phr). Preferably, between about 10 and 50 parts by weight of reinforcing fillers are used per 100 parts of rubber.
[0328] Examples of reinforcing fillers that may be included in the rubber composition according to some embodiments of the present invention include pyrogenic silica fillers and precipitated finely divided silica that are typically used for rubber compounding. However, the silica filler is preferably a type obtained by precipitation of a soluble silicate such as sodium silicate. For example, the silica filler can be produced according to the method described in U.S. Patent No. 2,940,830, which is incorporated herein in its entirety for all purposes. The precipitated hydrated silica pigment may have at least 50% by weight and generally greater than 80% by weight of SiO2 content, based on anhydrous basis. The silica filler may have a final particle size in the range of about 50 to 10,000 angstroms, preferably between 50 and 400, and more preferably between 100 and 300 angstroms. When measured by electron microscopy, silica may have an average final particle size in the range of about 0.01 to 0.05 microns, although the silica particles may be even smaller in size. The filler preferably has a Brunauer-Emmett-Teller ("BET") surface area in the range of 40 to 600 m2 / g, more preferably in the range of 50 to 300 m2 / g, when measured using nitrogen. The BET method for measuring surface area is described in the Journal of the American Chemical Society, Vol. 60, p. 304 (1930). The silica may also have a dibutyl ("DBP") absorption value in the range of about 200 to about 400, with a range of about 220 to 300 being preferred.
[0329] Various commercially available silicas and carbon blacks can be used as reinforcing fillers in various embodiments of the present invention. Suitable types of carbon black include, but are not limited to, super abrasive furnace, intermediate SAF, high abrasive furnace, easy processing channel, fast extrusion furnace, high modulus furnace, semi-reinforced furnace, fine thermal furnace, medium thermal furnace. For example, silicas commercially available from PPG Industries under the Hi-Sil trademark, such as those with designations 210, 243, etc., can be used; silicas available from Rhone-Poulenc, with the designations Z1165MP and Z165GR, and silicas available from Degussa AG, with the designations VN2 and VN3, etc. Rhone-Poulenc Z1165MP silica is a preferred silica, which is reported as being characterized by having a BET surface area of about 160-170, a DBP value of about 250-290, and a substantially spherical shape. Suitable examples of carbon black include, but are not limited to, N110, N121, N220, N231, N234, N242, N293, N299, S315, N326, N330, N332, N339, N343, N347, N351, N358, N375, N539, N550, N582, N630, N642, N650, N683, N754, N762, N765, N774, N787, N907, N908, N990, and N991.
[0330] In the rubber composition containing fillers, coupling agents are generally used. Silane coupling agents are particularly preferred. Such coupling agents can be pre-mixed or pre-reacted with fillers, for example, or added to rubber mixtures during rubber / filler processing or mixing stages. If the coupling agent and filler are added to the rubber mixture separately during the rubber / filler mixing or processing stage, it is considered that the coupling agent is then combined (merged) with the filler in situ. Any coupling agent known to those skilled in the art can be used in the composition of the present invention. The coupling agent is generally composed of such a coupling agent: it has a composition silane component (i.e., part) that can react with the surface of silica and a composition component that can react with rubber. Preferably, the coupling agent can react with sulfur-vulcanizable rubber, which contains carbon-carbon double bonds or unsaturated bonds (unsaturation). In this way, the coupling agent (coupling agent) can serve as a connecting bridge between silica and rubber, and thus enhance the rubber reinforcement aspect of silica.
[0331] The silane of the coupling agent may form a bond with the silica surface, possibly by hydrolysis, and the rubber reactive component of the coupling agent combines with the rubber itself. Typically, the rubber reactive component of the coupling agent is temperature sensitive and tends to combine with the rubber during the final and higher temperature sulfur vulcanization stage. However, a certain degree of combination or bonding may occur between the rubber reactive component of the coupling agent and the rubber during the initial rubber / silica / coupling agent mixing stage prior to the subsequent vulcanization stage.
[0332] Without departing from the scope of the present invention, and as understood by those skilled in the art, inert fillers may be included in the method of the present invention and the curable composition. If an inert filler is desired, any known or conventional filler that does not interfere with the vulcanization process described herein may be used, and such filler is desired in a finely divided form. Suitable fillers include, but are not limited to, the following: silicon dioxide and silicates, thermal black (thermal black) (i.e. furnace black, tank black or lamp black), clay, kaolin, diatomaceous earth, zinc oxide, cork, titanium dioxide, titanium dioxide, cotton wool, cellulose wool, leather fiber, plastic fiber, plastic powder, leather powder, fibrous fillers such as glass and synthetic fibers, metal oxides and carbonates and talcum. Other examples are calcium carbonate, silicon dioxide, carbon black, clay, talcum, mica, calcium oxide, aluminum oxide, magnesium carbonate, etc. The aforementioned filler may be heat treated or treated with silane, resin or cationic species to prevent or reduce the decomposition of some peroxides. The amount of inert filler is determined by its type and the desired end use of the composition and is generally from 0 to 200, preferably between 0 and 150, and more preferably between 50 and 100 parts by weight for 100 parts by weight of the elastomer or blend of elastomers.
[0333] Other additives in the curable composition
[0334] Other additives that may be added to the curable compositions of the present invention include antioxidants, UV stabilizers, antiozonants, plasticizers, mold release agents, tackifiers, antitackifiers, dispersants, solvents, softeners, fatty acids such as stearic acid, processing aids, colorants, etc., depending on the desired end use of the cured composition. Such additives may be included in the curable composition to achieve the desired final properties for a particular end-use application such as adhesive and sealant applications. A non-exhaustive list of such optional additional components is a tackifier and / or coupling agent; an adhesion promoter such as a functionalized liquid rubber resin (e.g., a maleated liquid polybutadiene resin); a plasticizer or extender oil such as a paraffin oil; and / or a stabilizer that resists thermal, thermal oxidation, or ozone degradation. The oligomeric product of the present invention may serve as a suitable substitute for a plasticizer or extender oil.
[0335] Examples of antidegradants that can be used in the rubber composition according to various embodiments of the present invention include, but are not limited to, monophenols, bisphenols, thiobisphenols, polyphenols, hydroquinone derivatives, phosphites, phosphate blends, thioesters, naphthylamines, diphenolamines, and other diarylamine derivatives, p-phenylenediamines, quinolines, and blended amines. Antidegradants are generally used in an amount ranging from about 0.1 phr to about 10 phr, with a range of about 2 to 6 phr being preferred.
[0336] Examples of peptizing agents include, but are not limited to, pentachlorophenol, which may be used in amounts ranging from about 0.1 phr to 0.4 phr, with a range of about 0.2 to 0.3 phr being preferred.
[0337] Examples of process oils include, but are not limited to, aliphatic-naphthenic aromatic resins, polyethylene glycols, petroleum, ester plasticizers, sulfurized vegetable oils, pine tar, phenolic resins, petroleum resins, polymeric esters, and rosin. The oligomeric products of the present invention may also serve as process oils. Process oils may be used in amounts ranging from about 0 to about 50 phr, with a range of about 5 to 35 phr being preferred.
[0338] The rubber composition according to an embodiment of the present invention can be compounded by conventional means known to those skilled in the art, including a mixer or compounder (such as mixer), mill, extruder, etc. The tire can be built, shaped, molded and cured by various methods, which will also be readily apparent to those skilled in the art.
[0339] To cure the curable rubber composition of the present invention, any conventional vulcanization or curing process known in the art may be used, such as heating in a press or mold using superheated steam or hot air. Thus, the curable rubber composition may be cured by a process comprising heating the curable rubber composition, which may be molded into a desired form at a temperature and for a time effective to cure the diene elastomer.
[0340] Particular embodiments of the present invention include tires, particularly tire treads, intended for use with passenger car or light truck tires, but the present invention is not limited to such tires. It is noted that particular embodiments of the tires of the present invention are intended to be mounted on motor vehicles (including passenger vehicles) or non-motor vehicles, such as bicycles, motorcycles, racing cars, industrial vehicles such as trucks, heavy vehicles such as buses and trucks, off-road vehicles such as agricultural, mining and construction machinery, aircraft or other transportation or handling vehicles.
[0341] The curable rubber composition disclosed herein can be used for various rubber products such as tires, particularly in tread compounds, and for other parts of tires, industrial rubber products, seals, timing belts, power transmission belts and other rubber goods. Therefore, the present invention includes products made from the curable rubber composition disclosed herein.
[0342] Example
[0343] The following pyrolyzed plastic oils were used in the examples:
[0344] Pyrolysis Oil 1: It has a boiling point in the range of 50°C to about 480°C and a diene value of about 2.7%. The chlorine content is in the range of about 115 ppm, and the silicon content is expected to be in the range of about 15 ppm. The oxygen content is expected to be in the range of about 1 wt%. The nitrogen content is expected to be in the range of about 1150 wt ppm.
[0345] Pyrolysis Oil 2: A light fraction obtained by distillation of pyrolysis oil (produced by non-catalytic pyrolysis of mixed waste plastics) and having a boiling point ranging from about 50° C. to about 260° C. The water content is expected to be below 100 ppm by weight. The diene value is expected to be in the range of about 4.8%.
[0346] Pyrolysis Oil 3: A light fraction of non-catalytic pyrolysis plastic oil (obtained by fractional condensation of pyrolysis effluent) and having a boiling point ranging from <36°C to about 260°C. The oil has been decanted to ensure that the water content is below 100 wt ppm. The diene value is expected to be in the range of about 7.8%.
[0347] Pyrolysis oil 4: It has a boiling point ranging from 40°C to about 401°C and a diene value of about 2.1%. The chlorine content is expected to be in the range of about 270 ppm, and the silicon content is expected to be in the range of about 12 ppm. The oxygen content is expected to be in the range of about 0.3 wt%. The nitrogen content is expected to be in the range of about 1250 wt ppm.
[0348] Method for measuring diene content
[0349] Unless otherwise specified, the following method was used to determine the diene content in the pyrolyzed plastic oils in all examples.
[0350] The determination of the diene content is carried out by means of GPC with a UV detector. A given amount of maleic anhydride is added to the pyrolyzed plastic oil and reacted with the diene via a Diels-Alder reaction. The reduction of the UV-active MA peak in the chromatogram is monitored and used to determine the diene concentration. In a first step, a calibration curve is prepared. The equipment used is
[0351] Agilent 1260 Series Degasser (Part No. G1322A); Agilent 1260 Series Isocratic Pump (Part No. G1310B); Agilent 1260 Series Autosampler (Part No. G1329B); Agilent 1260 Series Thermostat Column Compartment (Part No. G1316A); Agilent 1260 Series Multi-Wavelength Detector (Part No. G1365C); and Agilent 1260 Series Refractive Index Detector (Part No. G1362A).
[0352] Column Set: 1x Agilent ResiPore 50x4.6mm guard column (Part No. PL1513-1300); and 2x Agilent ResiPore 250x4.6mm 3um particle size columns (Part No. PL1513-5300).
[0353] Software: Cirrus 3.3, ChemStation B04.03
[52] .
[0354] Solvent: THF stabilized by 250 ppm BHT, flow rate: 0.45 ml / min.
[0355] Column chamber temperature: 40°C
[0356] Calibration: Polystyrene standards from Agilent EasiCal Standards
[0357] i) GPC-UV Calibration of Maleic Anhydride:
[0358] Samples of known concentration of maleic anhydride (MA) in THF were prepared and analyzed using GPC with a UV detector.
[0359] The chromatograms were analyzed for peak areas at 240 nm.
[0360] A plot of MA (ppm) versus peak area can generate a calibration curve ( Figure 2 ). The equation of the line can be used to determine the concentration of MA in the unknown solution.
[0361] ii) Preparation of samples for testing:
[0362] A 6 wt % solution of maleic anhydride in toluene was prepared.
[0363] 15 g of MA was added to 200 mL of toluene and heated to 55° C. for 4 hours. The solution was then cooled and the volume was brought to 250 mL.
[0364] The solution was allowed to stand overnight and filtered the following day. This removed some of the undissolved MA that had precipitated.
[0365] Once prepared, the solution should be used within two weeks.
[0366] The concentration of the MA solution was checked using the equation from the GPC-UV calibration (Equation 1) as follows:
[0367] Equation 1:
[0368] Where PA is the peak area at 240nm (15.8-16.6min) (mV.s), sample MF is the concentration of the sample and Inj.Vol is the sample injection volume (uL). The equation 0.1586x+0.3095 is the equation of the straight line from the MA calibration graph.
[0369] iii) Sample preparation and Diels-Alder (DA) reaction
[0370] 15 g of sample (pyrolysis oil) was weighed out and added to a 100 mL round bottom flask (RBF).
[0371] 20 mL of 6% MA in toluene solution and a stir bar were added to the 100 mL RBF with the sample.
[0372] Mix the solution gently, then remove (take out) 55-70 mg of the mixture and place into a 20 ml bottle. Record the exact amount of mixture added.
[0373] Add 9-10 g of THF to a 20 mL bottle, recording the exact amount of THF added.
[0374] The sample in THF in the 20 mL bottle will be used for the initial determination of MA to calculate the dienes. Note as initial value in the calculation. Run GPC-UV.
[0375] The mixture in a 100 mL RBF was then heated to reflux for 3 hours.
[0376] While refluxing, 55-70 mg of the solution was then placed into a second 20 mL vial. The exact amount added was recorded.
[0377] Add 9-10 g of THF to the second 20 mL bottle, record the exact amount of THF added. This sample is used for the final determination of MA to calculate dienes. Note as final value in calculations. Run GPC-UV.
[0378] The amount of reacted and unreacted MA was determined.
[0379] Calculate the initial amount of MA using Equation 1 and the initial sample.
[0380] Calculate the final amount of MA using Equation 1 and the final sample.
[0381] Convert the results from ppm to %, and calculate the amount of MA consumed using Equation 2:
[0382] Equation 2:
[0383] Determine the diene % of the sample
[0384] To determine the diene content, the amount of MA (g) used during the DA reaction needs to be known.
[0385] 20 mL of 6% MA solution in toluene = 1.8 g MA and 16.3 g toluene
[0386] The percentage of C5H8 dienes and higher MW dienes was determined.
[0387] Integration of the 240 nm peak area from 13.5-16 minutes and 16-18.5 minutes of the pure sample from GPC-UV provides the peak area percentages of the higher Mw dienes and C5H8 dienes, respectively.
[0388] The Mw (g / mol) of the higher Mw dienes was determined using the Mw (g / mol) from GPC and normalized using the Mw of the C5H8 peak and 68 g / mol.
[0389] Equation 3 is used to determine the diene percentage.
[0390] Equation 3:
[0391] Example 1. Oligomeric products using BF 3 Production
[0392] The purified pyrolysis oil is prepared by solution polymerization, in which the catalyst and monomer are continuously fed into a reaction vessel, and boron trifluoride diethyl etherate is used as a catalyst, wherein BF 3 The weight percentage to the total feed is 1.15±0.25%.
[0393] The flow rates of monomer feed and Friedel-Crafts catalyst were controlled so that the combined mass flow of catalyst feed to monomer was about 2 to 3 wt%. The reaction temperature was maintained at 40°C throughout the polymerization and all steps were performed under a nitrogen blanket.
[0394] An initial amount of pyrolysis oil (~10 wt% of the total) was added as a reaction tail to a round bottom flask (RBF) purged with nitrogen. The tail was then warmed to 40°C under nitrogen while stirring. The pyrolysis oil feed and Lewis acid catalyst (BF 3 -OEt 2) were each measured out in a separate flask. If a comonomer (i.e. styrene) was used, it was measured out and added to the flask with the pyrolysis oil feed. The pyrolysis oil and catalyst were fed into the reactor while maintaining a temperature of 40°C such that the catalyst was added at 2 to 3 wt% of the monomers and both feeds were added at approximately the same time. Upon completion of the feed additions, the mixture was stirred at 40°C for 45-60 minutes before cooling to room temperature. The polymerization was carried out under a nitrogen blanket.
[0395] The reaction mixture was then transferred to a separatory funnel and diluted with 0.1 M NH 4 The mixture was washed three times with 1% 4-H-D-OH and the aqueous phase was discarded. The organic mixture was then washed twice more with water and the organic phase was transferred to a separate three-necked round bottom flask for distillation. During the washings, there was an insoluble tarry-like residue that remained on the sides of the reaction flask and separatory funnel. In all cases of purification, unless otherwise stated, a tarry residue was left.
[0396] The organic mixture is purged with nitrogen while being heated to 230°C and the volatile organics are collected. Once the temperature reaches 230°C, distillation is continued until no more volatiles are distilled, at which time the nitrogen is replaced by steam. The volatiles collected before steam stripping are called distillate. Oligomeric products and steam condensate are collected until minimal oligomeric products are being collected. The collected oligomeric products are called oily polymers. The material remaining after steam stripping is the resin / wax product polymerized during purification. The collected distillate is a purified pyrolysis oil with reduced dienes.
[0397] Table 1 shows the catalyst and comonomer amounts used for the polymerization and the final diene concentration of the distillate after purification. After polymerization, the diene content had been reduced to less than 0.5% in all cases and in some cases had been removed to undetectable levels.
[0398] Table 1. Initial and final diene concentrations.
[0399]
[0400] Example 2. Oligomeric products using aluminum chloride (AlCl 3 ) as a catalyst for production.
[0401] Hexane (~10 wt% of total) was added to the RBF using a nitrogen purge. AlCl 3 Catalyst (approximately 1.25 wt% of total feed) was added to hexane and warmed to 35°C while stirring under nitrogen. The pyrolysis oil feed was measured out in a separate flask and fed at a rate of 2 mL / min. Upon completion of the feed addition, the mixture was stirred at 35°C for 50 minutes before cooling to room temperature. Polymerization was carried out under a nitrogen blanket.
[0402] The reaction mixture was then transferred to a separatory funnel and washed three times with 25% isopropanol aqueous solution (IPA), and the aqueous phase was discarded. The organic mixture was then washed twice more with water, and the organic phase was transferred to a separate three-necked round-bottom flask for distillation. The organic mixture was then distilled and steam stripped as in Example 1.
[0403] Example 3. Production of oligomeric products using Amberlyst 15 as catalyst.
[0404] The pyrolysis oil was added to the RBF and stirred under nitrogen while warming to 40°C. Amberlyst 15, approximately 1% by weight of the total feed, was added as a catalyst in two doses. Once the oil reached 40°C, an initial amount of Amberlyst 15 catalyst (2 / 3 of the total amount) was added, and then stirred at 40°C for 45 minutes under nitrogen. The remaining 1 / 3 of the catalyst was then added, and the reaction was stirred for another 75 minutes. The mixture was then cooled to room temperature and the catalyst was filtered. The organic mixture was then distilled and steam stripped as in Example 1.
[0405] Example 4. Oligomeric products were prepared using sulfuric acid (H 2 SO 4 ) production.
[0406] The pyrolysis oil was added to the RBF and stirred at room temperature. Sulfuric acid, approximately 2.5 wt % of the total feed, was then added to the stirred pyrolysis oil and immediately released heat. The reaction was stirred until the temperature dropped back to room temperature. The acid was neutralized and the oil was washed with dilute sodium carbonate (2x) followed by water (2x). The oil was then distilled and steam stripped as in Example 1.
[0407] The following table summarizes the various amounts of Lewis acid catalyst used in Examples 2-4.
[0408] Table 2. Summary of the amounts of Lewis acid catalysts used.
[0409] <![CDATA[AlCl 3 ]]> Amberlyst 15 sulfuric acid Hexane(g) 8.5 -- -- Catalyst(g) 0.95 0.84 1.25 Pyrolysis oil 3(g) 75.6 86.2 63.8
[0410] For Examples 2 to 4, the effect of the purification process via cationic polymerization was determined by Figure 3 and 4 The 82MHz 1 H NMR and FTIR measurements. Comparison of the fraction attributable to olefinic protons in the pyrolysis oil with the same fraction after cationic polymerization shows that the fraction of olefinic protons decreases in the case of all acid catalysts used. Similar conclusions were drawn from Figure 3 It is concluded that, in the case of cationic polymerization, the conjugated olefin peak area decreases. Therefore, Examples 2 to 4 demonstrate that in the presence of catalyst AlCl 3 In the case of , Amberlyst 15 and sulfuric acid, cationic polymerization allows for a reduction in diene content.
[0411] Example 5. Characterization of oligomeric products
[0412] The resin or wax product derived from the pyrolysis oil is the result of polymerization applied to the pyrolysis oil. When the resin or wax is produced and separated, the resulting liquid hydrocarbon is then the purified pyrolysis oil. In those embodiments, the oligomeric products are of various kinds. That is, the wax+product consists of the tarry residue remaining after the aqueous wash is dissolved in acetone / THF and added to the organic phase for distillation.
[0413] The separated residue remaining after distillation and steam stripping of the post-polymerization pyrolysis oil is either a resin or wax product, depending on the pyrolysis oil feed. The reaction conditions and product properties are shown in Table 3.
[0414] Table 3. Reaction conditions and product properties of polymerized oils
[0415]
[0416] As shown in Table 4, the properties of the oligomeric products depend on the plastic pyrolysis oil feed, and in all cases, the diene content has been reduced. The aromatic content in the wax+ and wax products from pyrolysis oil 1 is relatively low, and these are highly saturated hydrocarbon products. The melting and crystallization temperatures of the wax+ and wax products are about room temperature. The polymerized resin and resin-styrene products from pyrolysis oil 2 contain higher amounts of aromatic content.
[0417] Table 4. Comparison of polymerized products and commercially available products.
[0418]
[0419] Example 6. Preparation of a rubber composition for tire applications
[0420] The resin and wax products described in Table 1 were evaluated using a model tire tread formulation compared to a standard process oil and Wingtack 10. The formulations were compounded in three stages. The initial stage was compounded in an internal mixer at 150-155°C for 5 minutes, the second stage was completed using an internal mixer at 90-100°C for 4 minutes, and the third stage was at 60°C for 5 minutes. The mixing at each stage was similar for all samples, and the compounding became less fragmented as the stages progressed.
[0421] Initial stage:
[0422]
[0423] Phase 2:
[0424] Components phr Stearic acid 2.30 Antiozonant (6PPD) 2.00
[0425] Phase 3:
[0426] Components phr sulfur 1.30 Zinc Oxide 2.30 Delayed Action Accelerator (TBBS) 1.70 Fast curing accelerator (TBzTD) 0.50 Basic accelerator (DPG) 2.00
[0427] In addition to Wingtack 10 (a petroleum-based liquid resin), commercial process oils Sunpar 2280 (paraffinic) and Plaxolene TD346 (processed distillate aromatic extracted, TDAE) were used as comparative examples of pyrolysis oil products for use in tire tread formulations. The oils used in the batches are shown in Table 5 below.
[0428] Table 5. Processing oils used in tire tread batches.
[0429] batch Processing oil 1 WT10 2 Sunpar 2280 3 Plaxolene TD346 4 Wax+ 5 wax 6 Resin 7 Resin-Styrene
[0430] Oscillating disk rheometer (ODR) testing was performed to compare the crosslinking behavior of the different batches at 160°C. The results are shown in Table 6 below. The working time (ts2) remained constant for all tire tread formulations regardless of the process oil used; however, the use of resin and resin-styrene from pyrolysis oil increased the cure time (t'90) compared to standard process oil and WT10. The delta torque of the resin and resin-styrene based formulations was less than that of WT10, whereas Wax+ and Wax were similar.
[0431] Table 6 ODR results and the influence of products on cross-linking behavior.
[0432]
[0433] The cured properties of the formulations are shown in Table 7 below. The formulations were cured in a heated press at 160°C for 25 minutes. As a process oil in tire tread formulations, the resin and resin-styrene products were comparable to WT10. The wax and wax+products were comparable to TDAE when used as a process oil in these formulations.
[0434] Table 7. Cured properties of tire tread formulations with products.
[0435]
[0436] Dynamic Mechanical Analysis (DMA) is used to determine the elastic modulus G' (Payne effect) as a function of strain deformation and to measure tan δ. The elastic modulus as a function of strain deformation is used to evaluate the effectiveness of silica dispersion; at low deformations, reduced interactions between silica particles lead to lower G' values, indicating better dispersion. Tan δ is conventionally used in the industry as a performance indicator; higher values of tan δ at 0°C are associated with better wet traction, and lower values of tan δ at 60°C are associated with better rolling resistance. The results are reported in Table 8 below.
[0437] The wax product from the polymerization of the pyrolysis oil improved the dispersion of silica in the formulation relative to the control, and the resin product performed like the standard oil. The resin and resin-styrene performed like WT10 and had improved wet traction in tire tread formulations compared to the standard process oil, while the wax product showed improved rolling resistance compared to the standard process oil.
[0438] Table 8. DMA results using the product as process oil.
[0439]
Claims
1. A rubber composition, characterized in that It contains: a) at least one elastomer selected from synthetic elastomers and natural elastomers; b) a curing agent; and c) an oligomeric product prepared from liquefied waste polymer, said oligomeric product having a number average molecular weight Mn in the range of 100 to 10 000 g / mol measured using gel permeation chromatography and polystyrene calibration, and wherein said oligomeric product exhibits a crystallization temperature below 35°C, or a glass transition temperature (Tg) below -20°C when determined by differential scanning calorimetry.
2. The rubber composition according to claim 1, characterized in that The at least one elastomer is present in an amount ranging from 1 to 150 phr.
3. The rubber composition according to claim 1 or 2, characterized in that The content of the curing agent is 0.1 to 25 phr, and the content of the oligomeric product ranges from 0.1 to 50 phr.
4. The rubber composition according to any one of claims 1 to 3, characterized in that When passing 1 The oligomeric product exhibits an olefinic content of up to 20.0 wt. %; preferably in the range of 0.1 to 10.0 wt. % as determined by H NMR.
5. The rubber composition according to any one of claims 1 to 4, characterized in that When passing 1 The oligomeric product exhibits an aliphatic content in the range of 15 to 100 wt %; preferably in the range of 50.0 to 99.0 wt % as determined by H NMR.
6. The rubber composition according to any one of claims 1 to 5, characterized in that When passing 1 The oligomeric product exhibits an aromatic content of less than 50 wt %; preferably in the range of 0.1 to 10.0 wt % as determined by H NMR.
7. The rubber composition according to any one of claims 1 to 6, characterized in that The oligomeric product exhibits a viscosity ranging from 10 to 50 000 cps; preferably ranging from 10 to 10 000 cps at 30°C measured using a Brookfield viscometer.
8. The rubber composition according to any one of claims 1 to 7, characterized in that The oligomeric product exhibits a number average molecular weight (Mn) ranging from 100 to 700 g / mol; preferably from 100 to 550 g / mol, measured using gel permeation chromatography and polystyrene calibration.
9. The rubber composition according to any one of claims 1 to 8, characterized in that The oligomeric product comprises a comonomer selected from the group consisting of styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-tert-butylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2,4-diisopropylstyrene, 2,4,6-trimethylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, 1-vinylnaphthalene, 2-vinylnaphthalene, vinylanthracene, 4-methoxystyrene, monochlorostyrene, dichlorostyrene, divinylbenzene, indene, methyl-indene, and mixtures thereof; preferably, the oligomeric product comprises a comonomer, the comonomer being or comprising styrene.
10. The rubber composition according to any one of claims 1 to 9, characterized in that The oligomeric product comprises a comonomer present in a concentration ranging from 0.01 to 90 mole %, preferably from 1.0 to 80 mole %, based on the total weight of the oligomeric product.
11. Tire comprising the rubber composition according to any one of the preceding claims from 1 to 10, preferably comprising said oligomeric product in a content ranging from 1 to 50 phr.
12. A process for preparing a rubber composition according to any one of claims 1 to 11, comprising the following steps: a) providing a feed stream (1) comprising liquefied waste polymer, wherein the feed stream (1) contains at least 0.1 wt. % to at most 80 wt. % of dienes, based on the total weight of the feed stream (1); c) polymerizing the feed stream (1) under polymerization conditions to obtain a first product stream (3) comprising oligomeric products (33) and purified liquefied waste polymer; d) optionally, conducting a neutralization reaction by contacting the first product stream (3) with a basic compound (25) to obtain a neutralized product stream (4), and removing the basic compound from the neutralized product stream (4) to obtain a second product stream (5); g) separating the oligomeric product (33) from the purified liquefied waste polymer (34); and h) preparing a rubber composition comprising: at least one elastomer selected from synthetic elastomers and natural elastomers; a curing agent; and the oligomeric product recovered in step g).
13. The process according to claim 12, characterized in that The polymerization reaction in step c) is a cationic polymerization; and / or the process further comprises a step (b) of drying the feed stream (1) to obtain a dried feed stream (2), wherein step b) is carried out before step c) of polymerization, so that step c) of polymerization is carried out on the dried feed stream (2).
14. The process according to claim 13, characterized in that A drying step b) is performed, and step b) comprises a sub-step b1) of decantation and / or centrifugation; preferably, the first sub-step b1) is followed by a second sub-step b2) of drying using molecular sieves to reach a water content of less than 0.1% by volume according to ASTM D95-13 (2018).
15. The process according to any one of claims 12 to 14, characterized in that The polymerization reaction in step c) is a cationic polymerization carried out in the presence of an acidic catalyst; preferably, the acidic catalyst is a Bronsted acid or a Lewis acid.
16. The process according to claim 15, characterized in that The polymerization reaction in step c) is a cationic polymerization carried out in the presence of an acidic catalyst, wherein the acidic catalyst is a Lewis acid selected from BF3, a complex of boron trifluoride, AlCl3, SnCl4, ZnCl2, FeCl3 and TiCl3, an alkylaluminum chloride, H2SO4, or any mixture thereof; preferably, the acidic catalyst is or comprises boron trifluoride etherate.
17. The process according to claim 15 or 16, characterized in that The acidic catalyst is present in a concentration ranging from 0.5 wt% to 5.0 wt%, based on the total weight of the feed stream (1), and / or the polymerization reaction of step c) is carried out until the diene content of the purified liquefied waste polymer is less than 5.0 wt%, based on the total weight of the first product stream (3).
18. The process according to any one of claims 12 to 17, characterized in that The polymerization conditions of step (c) include a contact time ranging from 5 minutes to 5 hours; and / or a temperature ranging from 5 to 100° C. at atmospheric pressure.
19. The process according to any one of claims 12 to 18, characterized in that The polymerization reaction of step c) is carried out in the presence of one or more comonomers; preferably, the one or more comonomers comprise vinyl aromatic and / or the one or more comonomers are present in a concentration of 1.0 to 25.0 wt. %, based on the total weight of the liquefied waste polymer.
20. The process according to any one of claims 15 to 19, characterized in that Step d) is carried out with a concentration of the basic compound in the range of 0.1 to 50.0% by weight, based on the total weight of the neutralized product stream (4).
21. The process according to any one of claims 15 to 20, characterized in that Step d) is carried out and the basic compound: - has a pKa in water ranging from 7.5 to 14; and / or - is selected from LiOH, NaOH, CsOH, Ba(OH)2, Na2O, KOH, K2O, CaO, Ca(OH)2, MgO, Mg(OH)2, NH4OH, or any mixture thereof.
22. The process according to any one of claims 15 to 21, characterized in that Step d) is performed in a continuous mode, and / or step d) is performed and the basic compound is removed from the neutralized product stream (4) to obtain a second product stream (5) by decantation and / or centrifugation.
23. The process according to any one of claims 12 to 22, characterized in that It further comprises a step e) of washing the first product stream (3) or the second product stream (5) with a solvent (27) to obtain a washed stream (6); preferably, the washing is carried out at a temperature ranging from 5°C to 95°C.
24. The process according to claim 23, characterized in that The solvent (27) is selected from water or an acidic aqueous solution, wherein the acidic aqueous solution contains one or more organic acids selected from citric acid (C6H8O7), formic acid (CH2O2), acetic acid (CH3COOH), aminosulfonic acid (H3NSO3), and any combination thereof, and / or one or more inorganic acids selected from hydrochloric acid (HCl), nitric acid (HNO3), sulfuric acid (H2SO4), phosphoric acid (H3PO4), and any combination thereof.
25. The process according to claim 23 or 24, characterized in that The washing is performed until the pH of the washed stream (6) is in the range of 5.0 to 9.0; and / or the washing is followed by decantation and / or centrifugation to separate the solvent from the washed stream (6).
26. The process according to any one of claims 12 to 25, characterized in that It further comprises a step f) of filtering the stream obtained in the previous step to obtain a filtered stream (7), wherein the filtration is carried out to remove solids from the first product stream (3) or from the second product stream (5) or from the washed stream (6), and / or to agglomerate remaining traces of solvent, if any; preferably, the filtration step is followed by a dehydration step.
27. The process according to any one of claims 12 to 26, characterized in that The step g) of separating is carried out via distillation or steam distillation or vacuum stripping or fractional distillation or any combination thereof.
28. The process according to any one of claims 12 to 27, characterised in that After separation step g), the purified liquefied waste polymer is collected and blended in a fuel pool; preferably, the purified liquefied waste polymer is separated into a naphtha fraction having a boiling range of less than 150°C and a diesel fraction having a boiling range between 150 and 350°C, wherein the naphtha fraction is incorporated into the naphtha pool and the diesel fraction is incorporated into the diesel pool.
29. The process according to any one of claims 12 to 28, characterized in that The liquefied waste polymer is pyrolyzed plastic oil. Preferably, step a) of providing a feed stream (1) containing the liquefied waste polymer comprises a preliminary step of preparing the liquefied waste polymer, comprising: a1) Provide waste plastic streams; a2) pyrolyzing the waste plastic stream at a temperature of at least 200° C.; a3) collecting the pyrolyzer effluent and separating it into a C1 to C4 hydrocarbon fraction, a fraction having a boiling range above 350° C., and a remaining fraction as the pyrolyzed plastic oil; a4) optionally sending the fraction with a boiling range above 350°C to a fluid catalytic cracking unit, or a hydrocracking unit, a coker, or a visbreaker, or blending said fraction with a boiling range above 350°C in crude oil or in crude oil fractions for further refining.
30. The process according to any one of claims 12 to 29, characterized in that The liquefied waste polymer in the feed stream (1) has a final boiling point of at most 700°C; and / or the feed stream (1) contains 0.1 to 50.0 wt. % of diene, based on the total weight of the feed stream (1).
31. The process according to any one of claims 12 to 30, characterized in that The liquefied waste polymer is pyrolysis oil, preferably pyrolysis plastic oil, or any pyrolysis oil prepared from waste plastic, rubber, biomass, used tires, or any mixture thereof.
Citation Information
Patent Citations
Conversion of plastics to olefin and aromatic products with product recycle
US20140228606A1
Silane Modified Elastomeric Polymers
US20160369015A1
Sulfur-crosslinkable rubber mixture, vulcanizate of the rubber mixture, and vehicle tire
US20200377700A1
Method of preparing silica pigments
US2940830A
Conversion of plastics to olefin and aromatic products
US8895790B2